Resin composition

By introducing a copolymer resin composition of structure (I) and polypeptide silicone alkyl group into the self-cleaning coating resin composition, the shortcomings of the existing resin composition in terms of storage stability, coating hardness and anti-fouling adhesion properties are solved, and better coating performance is achieved.

JP2025067485APending Publication Date: 2025-04-24MITSUBISHI CHEM CORP

Patent Information

Application Number
JP2023177507
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-04-24

AI Technical Summary

Technical Problem

The existing self-cleaning coating resin compositions have shortcomings in storage stability, coating hardness and anti-fouling adhesion properties.

Method used

A copolymer resin composition containing structure (I) and polypeptide silicone alkyl groups is used, and the properties of the resin are optimized by adjusting the mass ratio of the copolymer resin and the content of structural units.

Benefits of technology

It has achieved the formation of a self-cleaning coating with excellent anti-fouling adhesion properties, good storage stability and high coating hardness, extending the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025067485000001
    Figure 2025067485000001
  • Figure 2025067485000002
    Figure 2025067485000002
  • Figure 2025067485000003
    Figure 2025067485000003
Patent Text Reader

Abstract

To provide a resin composition which can form a coating film excellent in antifouling properties and has good storage stability and excellent coating film hardness.SOLUTION: The resin composition contains: a copolymer (X) having at least one structure (I) represented by -CO-O-M-O-CO- or -CO-O-M-R0 (M represents Zn, Cu, Mg or Ca, and R0 represents a monovalent organic acid residue) and a polysiloxane group; and a copolymer (Y) different from the copolymer (X). The copolymer (Y) has a hydrolyzable group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. [Background technology]

[0002] 2. Description of the Related Art It is known that marine structures and ships are coated with antifouling paint to prevent adhesion of marine organisms that cause corrosion of parts in contact with seawater and slow down navigation speed. As an antifouling paint, a self-polishing type antifouling paint is known. The self-polishing type antifouling paint typically contains a hydrolyzable resin and an antifouling agent. The coating film obtained from such an antifouling paint exhibits a long-term antifouling effect by gradually dissolving the coating film surface in seawater and renewing the surface (self-polishing), and the antifouling agent is always exposed on the coating film surface.

[0003] The following have been proposed as self-polishing antifouling paint resins that contain a vinyl polymer containing a unit having a carboxyl group ionically bonded to a divalent metal and other polymers. Patent Document 1 proposes a resin composition for an antifouling coating material, which contains a vinyl polymer (A) having an acid value of 35 mgKOH / g or more and a vinyl polymer (B) having an acid value of less than 20 mgKOH / g, and which contains a unit having a carboxyl group ionically bonded to a divalent metal. Patent Document 2 proposes a polymer-containing composition in which a (meth)acrylic copolymer (A-1) contains a unit having a carboxyl group ionically bonded to a divalent metal and has a weight average molecular weight of 1,000 to 5,000, and further contains a vinyl polymer (B), the vinyl polymer (B) having an acid value of less than 25 mg KOH / g and a number average molecular weight of 2,000 to 20,000. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2013 / 183637 [Patent Document 2] International Publication No. 2018 / 008166 Summary of the Invention [Problem to be solved by the invention]

[0005] The resin compositions described in Patent Documents 1 and 2 do not necessarily satisfy the performance (storage stability, coating hardness, etc.) required for an antifouling coating material. An object of the present invention is to provide a resin composition which is capable of forming a coating film having excellent antifouling properties, and which has good storage stability and excellent coating film hardness. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] A resin composition comprising: a copolymer (X) having at least one of structures (I) represented by the following formula (1) or the following formula (2) and a polysiloxane group; and a copolymer (Y) different from the copolymer (X), the copolymer (Y) having a hydrolyzable group. -CO-OMO-CO- ···(1) -CO-OMR 0 (2) (In the formula, M represents Zn, Cu, Mg, or Ca; R 0 represents a monovalent organic acid residue.) [2] The resin composition according to [1], wherein X / Y, which represents a mass ratio of the copolymer (X) to the copolymer (Y), is 95 / 5 to 40 / 60. [3] The resin composition according to [1] or [2], wherein the hydrolyzable group of the copolymer (Y) is at least one selected from the group consisting of groups represented by the following formulas (1) to (5) and a triorganosilyloxycarbonyl group: -CO-OMO-CO- ···(1) -CO-OMR 0 (2)

[0007] [ka]

[0008] In the formulas (1) and (2), M represents Zn, Cu, Mg, or Ca, and R 0 represents a monovalent organic acid residue. In the formulas (3) to (5), X represents -O-, -S-, or -NR 13 - indicates R 13 represents a hydrogen atom or an alkyl group, R 1’ and R 2’ each represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 3’ and R 5’ each represents an alkyl group, a cycloalkyl group, or an aryl group having 1 to 20 carbon atoms; R 4’ and R 6’ Each represents an alkylene group having 1 to 10 carbon atoms. [4] The resin composition according to any one of [1] to [3], wherein the copolymer (Y) has an acid value of 20 mgKOH / g or more. [5] The resin composition according to any one of [1] to [4], wherein, of the copolymer (X) and the copolymer (Y), at least the copolymer (X) has a structural unit (B) based on a monomer having a polysiloxane group and an ethylenically unsaturated bond, and the structural unit (B) accounts for 15 mass% or more and 50 mass% or less of the total mass of all structural units of the copolymer (X) and the copolymer (Y). [6] The resin composition according to any one of [1] to [5], wherein the copolymer (X) has a structural unit (B) based on a monomer having a polysiloxane group and an ethylenically unsaturated bond, and the structural unit (B) accounts for 15 mass% or more of the total mass of all structural units of the copolymer (X). [7] The resin composition according to any one of [1] to [6], wherein the copolymer (Y) does not have a structural unit (B) based on a monomer having a polysiloxane group and an ethylenically unsaturated bond, or, if the copolymer (Y) has a structural unit (B), the content of the structural unit (B) is 10 mass% or less relative to the total mass of all structural units of the copolymer (Y). Effect of the Invention

[0009] According to the present invention, a resin composition can be obtained which is capable of forming a coating film having excellent antifouling properties, and which has good storage stability and excellent coating film hardness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The following definitions of terms apply throughout the specification and claims. The term "(meth)acrylic copolymer" refers to a copolymer in which at least a part of the constituent units is derived from a (meth)acrylic monomer. The (meth)acrylic copolymer may further contain a constituent unit derived from a monomer other than the (meth)acrylic monomer (e.g., a vinyl monomer such as styrene). The term "structural unit" refers to a structural unit derived from a monomer formed by polymerization of the monomer, or a structural unit in which a portion of the structural unit is converted into a different structure by treating the polymer. The term "monomer" refers to a compound having polymerizability (polymerizable monomer). "(Meth)acrylic monomer" means a monomer having a (meth)acryloyl group. "(Meth)acryloyl group" is a general term for acryloyl group and methacryloyl group. "(Meth)acrylate" is a general term for acrylate and methacrylate. "(Meth)acrylic acid" is a general term for acrylic acid and methacrylic acid. "(Meth)acrylonitrile" is a general term for acrylonitrile and methacrylonitrile. "(Meth)acrylamide" is a general term for acrylamide and methacrylamide.

[0011] [Resin composition] A resin composition according to one embodiment of the present invention (hereinafter also referred to as "resin composition") contains copolymer (X), copolymer (Y), and an organic solvent. The copolymer (X) and the copolymer (Y) contained in the resin composition are different resins, and each may be one type or two or more types. The same applies to the organic solvent. The resin composition may further contain other components in addition to the copolymer (X), the copolymer (Y) and the organic solvent, as necessary.

[0012] <Copolymer (X)> The copolymer (X) has at least one of the structures represented by the following formula (1) or (2) (hereinafter also referred to as "structure (I)") and a polysiloxane group. -CO-OMO-CO- ···(1) -CO-OMR 0 (2) Here, M represents Zn, Cu, Mg, or Ca, and R 0 represents a monovalent organic acid residue. The structure (I) and the polysiloxane group contained in the copolymer (X) may each be of one type or two or more types. The structure (I) and the polysiloxane group may be contained in the structural unit of the copolymer (X), may be contained at the main chain terminal, or may be contained in both. From the viewpoint of antifouling properties, it is preferable that they are contained at least in the structural unit. When the structure (I) and the polysiloxane group are each contained in a constituent unit, it is preferable that the structure (I) and the polysiloxane group are contained in different constituent units. As the copolymer (X), a copolymer having a structural unit (A) based on a metal atom-containing polymerizable monomer (a) (hereinafter also referred to as "monomer (a)") having the structure (I) and an ethylenically unsaturated bond (polymerizable carbon-carbon double bond), and a structural unit (B) based on a polysiloxane group-containing polymerizable monomer (b) (hereinafter also referred to as "monomer (b)") having a polysiloxane group and an ethylenically unsaturated bond (polymerizable carbon-carbon double bond) is preferred. Copolymer (X) may further contain, as necessary, a structural unit (hereinafter also referred to as "structural unit (C)") based on a polymerizable monomer (hereinafter also referred to as "monomer (c)") other than monomer (a) and monomer (b).

[0013] (Structural unit (A)) The monomer (a) contains a structure (I) represented by the following formula (1) or (2) and an ethylenically unsaturated bond (polymerizable carbon-carbon double bond). -CO-OMO-CO- ···(1) -CO-OMR 0 (2) Here, M represents Zn, Cu, Mg, or Ca, and R 0 represents a monovalent organic acid residue.

[0014] In formulas (1) and (2), O or R adjacent to M 0 and M are ionic bonds. Since the copolymer (X) has the structure (I) (a carboxylate structure that forms an ionic bond with M), the coating film containing the copolymer (X) exhibits self-polishing properties.

[0015] As M, Zn or Cu is preferable since it improves the water resistance of the coating film.

[0016] R 0 The organic acid residue of refers to the portion remaining after removing one proton from an organic acid (for example, the portion remaining after removing one proton from the carboxy group of a carboxylic acid), and is ionic bonded to M in place of this proton. The organic acid is preferably a carboxylic acid, and examples thereof include monocarboxylic acids such as monochloroacetic acid, monofluoroacetic acid, acetic acid, propionic acid, octylic acid, versatic acid, isostearic acid, palmitic acid, cresothiic acid, α-naphthoic acid, β-naphthoic acid, benzoic acid, 2,4,5-trichlorophenoxyacetic acid, 2,4-dichlorophenoxyacetic acid, quinolinecarboxylic acid, nitrobenzoic acid, nitronaphthalenecarboxylic acid, pyruvic acid, naphthenic acid, abietic acid, hydrogenated abietic acid, and (meth)acrylic acid. R 0 In terms of storage stability, the alkyl group is preferably an organic acid residue other than a (meth)acryloyloxy group.

[0017] The structural unit (A) has a structure in which the ethylenically unsaturated bond of the monomer (a) is cleaved to form a single bond. The structural unit (A) is preferably at least one selected from the group consisting of a structural unit (A1) represented by the following formula (11) and a structural unit (A2) represented by the following formula (21).

[0018] [ka]

[0019] Here, M represents Zn, Cu, Mg, or Ca, and R 1 ~R 3 each independently represents a hydrogen atom or a methyl group; R 32 represents a monovalent organic acid residue. R 32 is R 0 is the same as:

[0020] The copolymer (X) is preferably a (meth)acrylic copolymer. An example of the monomer that forms the structural unit (A1) is the monomer (a1) represented by the following formula (a1). An example of the monomer that forms the structural unit (A2) is the monomer (a2) represented by the following formula (a2). CH2=C(R 1 )-CO-OMO-CO-C(R 2 ) = CH2 (a1) CH2=C(R 3 )-CO-OMR 32 (a2) M, R 1 ~R 3 , R 32 are as described above.

[0021] Specific examples of the monomer (a1) include the following: Zinc acrylate [(CH2=CHCOO)2Zn], zinc methacrylate [(CH2=C(CH3)COO)2Zn], copper acrylate [(CH2=CHCOO)2Cu], copper methacrylate [(CH2=C(CH3)COO)2Cu], magnesium acrylate [(CH2=CHCOO)2Mg], magnesium methacrylate [(CH2=C(CH3)COO)2Mg], calcium acrylate [(CH2=CHCOO)2Ca], calcium methacrylate [(CH2=C(CH3)COO)2Ca], etc. Among the above, zinc acrylate, zinc methacrylate, copper acrylate and copper methacrylate are preferred from the viewpoint of the water resistance of the coating film containing the copolymer (X). Any one of these monomers may be used alone, or two or more of them may be used in combination.

[0022] The monomer (a1) can be obtained, for example, by a method in which an inorganic metal compound containing a metal element corresponding to M in the formula (a1) is reacted with (meth)acrylic acid in a diluent such as an organic solvent or a reactive diluent having a polymerizable unsaturated group such as an ethylenically unsaturated monomer. The mixture containing the metal-containing polymerizable monomer obtained by this method has excellent compatibility with organic solvents and other monomers, and can easily carry out polymerization. The reaction is preferably carried out in the presence of water, and the content of water in the reaction product is preferably in the range of 0.01 to 30 mass%. Examples of the inorganic metal compound include oxides, hydroxides, chlorides, etc. of metals selected from Zn, Cu, Mg, and Ca.

[0023] Specific examples of the monomer (a2) include the following: Metal monochloroacetates (meth)acrylates such as magnesium monochloroacetate (meth)acrylate, calcium monochloroacetate (meth)acrylate, zinc monochloroacetate (meth)acrylate, and copper monochloroacetate (meth)acrylate; metal monofluoroacetates such as magnesium monofluoroacetate (meth)acrylate, calcium monofluoroacetate (meth)acrylate, zinc monofluoroacetate (meth)acrylate, and copper monofluoroacetate (meth)acrylate; magnesium acetate (meth)acrylate ) acrylate, calcium acetate (meth)acrylate, zinc acetate (meth)acrylate, copper acetate (meth)acrylate and other metal acetate (meth)acrylates; magnesium propionate (meth)acrylate, calcium propionate (meth)acrylate, zinc propionate (meth)acrylate, copper propionate (meth)acrylate and other metal propionate (meth)acrylates; magnesium octylate (meth)acrylate, calcium octylate (meth)acrylate, zinc octylate (meth)acrylate metal (meth)acrylates of octylate, copper (meth)acrylate of octylate, etc.; metal (meth)acrylates of versatic acid, such as magnesium (meth)acrylate of versatic acid, calcium (meth)acrylate of versatic acid, zinc (meth)acrylate of versatic acid, copper (meth)acrylate of versatic acid, etc.; magnesium (meth)acrylate of isostearate, calcium (meth)acrylate of isostearate, zinc (meth)acrylate of isostearate, copper (meth)acrylate of isostearate isostearate metal (meth)acrylate, such as acrylate; palmitate metal (meth)acrylate, such as magnesium palmitate (meth)acrylate, calcium palmitate (meth)acrylate, zinc palmitate (meth)acrylate, and copper palmitate (meth)acrylate; cresotate metal (meth)acrylate, such as magnesium cresotate (meth)acrylate, calcium cresotate (meth)acrylate, zinc cresotate (meth)acrylate, and copper cresotate (meth)acrylate;α-Naphthoic acid metal (meth)acrylates such as α-naphthoic acid magnesium (meth)acrylate, α-naphthoic acid calcium (meth)acrylate, α-naphthoic acid zinc (meth)acrylate, α-naphthoic acid copper (meth)acrylate; β-naphthoic acid metal (meth)acrylates such as β-naphthoic acid magnesium (meth)acrylate, β-naphthoic acid calcium (meth)acrylate, β-naphthoic acid zinc (meth)acrylate, β-naphthoic acid copper (meth)acrylate; benzoic acid magnesium (meth)acrylate, benzoic acid calcium (meth)acrylate, zinc benzoate (meth)acrylate, copper benzoate (meth)acrylate, and other metal benzoate (meth)acrylates; 2,4,5-trichlorophenoxyacetic acid magnesium (meth)acrylate, 2,4,5-trichlorophenoxyacetic acid calcium (meth)acrylate, 2,4,5-trichlorophenoxyacetic acid zinc (meth)acrylate, 2,4,5-trichlorophenoxyacetic acid copper (meth)acrylate, and other metal 2,4,5-trichlorophenoxyacetic acid (meth)acrylates; 2,4-dichlorophenoxyacetic acid magnesium (meth)acrylate, 2,4,5-trichlorophenoxyacetic acid calcium (meth)acrylate, 2,4,5-trichlorophenoxyacetic acid zinc (meth)acrylate, 2,4,5-trichlorophenoxyacetic acid copper (meth)acrylate, and other metal 2,4,5-trichlorophenoxyacetic acid (meth)acrylates; 2,4-dichlorophenoxyacetic acid metal (meth)acrylates such as quinoline carboxylate magnesium (meth)acrylate, quinoline carboxylate calcium (meth)acrylate, quinoline carboxylate zinc (meth)acrylate, and quinoline carboxylate copper (meth)acrylate; quinoline carboxylate metal (meth)acrylates such as quinoline carboxylate magnesium (meth)acrylate, quinoline carboxylate calcium (meth)acrylate, quinoline carboxylate zinc (meth)acrylate, and quinoline carboxylate copper (meth)acrylate; Metal nitrobenzoate (meth)acrylates such as magnesium nitrobenzoate (meth)acrylate, calcium nitrobenzoate (meth)acrylate, zinc nitrobenzoate (meth)acrylate, and copper nitrobenzoate (meth)acrylate; metal nitronaphthalene carboxylate (meth)acrylates such as magnesium nitronaphthalene carboxylate (meth)acrylate, calcium nitronaphthalene carboxylate, zinc nitronaphthalene carboxylate (meth)acrylate, and copper nitronaphthalene carboxylate (meth)acrylate;Metal pyruvate (meth)acrylates such as magnesium pyruvate (meth)acrylate, calcium pyruvate (meth)acrylate, zinc pyruvate (meth)acrylate, and copper pyruvate (meth)acrylate; Among the above, from the viewpoint of the water resistance of the coating film containing the copolymer (X), a monomer in which M is Zn or Cu is preferred. Any one of these monomers may be used alone, or two or more of them may be used in combination.

[0024] The monomer (a2) is, for example, a compound obtained by mixing an inorganic metal compound containing a metal element corresponding to M in the formula (a2), (meth)acrylic acid, and an organic acid residue R 32 and an organic acid corresponding to the above in a diluent such as an organic solvent or a reactive diluent having a polymerizable unsaturated group such as an ethylenically unsaturated monomer. The inorganic metal compound can be the same as the inorganic metal compound for obtaining the monomer (a1).

[0025] The copolymer (X) may also contain the structural unit (A1) and the structural unit (A2). That is, the copolymer (X) may also contain a structural unit based on the monomer (a1) and a structural unit based on the monomer (a2).

[0026] When the copolymer (X) contains the structural unit (A1) and the structural unit (A2), the molar ratio of the structural unit (A1) to the structural unit (A2) in the copolymer (X), structural unit (A1) / structural unit (A2), is preferably from 10 / 90 to 90 / 10, more preferably from 20 / 80 to 80 / 20, and even more preferably from 30 / 70 to 70 / 30. When this molar ratio is equal to or less than the upper limit, the viscosity of the resin composition containing the copolymer (X) and the organic solvent tends to decrease, whereas when it is equal to or more than the lower limit, the self-polishing property of the coating film containing the copolymer (X) tends to be maintained for a long period of time.

[0027] When the copolymer (X) contains a structural unit based on the monomer (a1) and a structural unit based on the monomer (a2), a monomer mixture containing the monomer (a1) and the monomer (a2) may be used in the production of the copolymer (X).

[0028] The monomer mixture containing the monomer (a1) and the monomer (a2) may be, for example, an inorganic metal compound containing a metal element corresponding to M in the formula (a1) and the formula (a2), (meth)acrylic acid, and an organic acid residue R 32 and an organic acid corresponding to the above in a diluent such as an organic solvent or a reactive diluent such as an ethylenically unsaturated monomer.

[0029] In that case, R 32 The amount of organic acid used is preferably 0.01 to 3 times by mol, more preferably 0.01 to 0.95 times by mol, and even more preferably 0.1 to 0.7 times by mol, relative to the inorganic metal compound. When the content of this organic acid is 0.01 times by mol or more, solid precipitation is suppressed in the manufacturing process of this monomer mixture, and the self-polishing property and crack resistance of the obtained coating film are improved. When the content is 3 times by mol or less, the antifouling property of the obtained coating film tends to be maintained for a longer period of time.

[0030] (Polysiloxane group) The polysiloxane group is a group having a Si-O-Si bond. Examples of the polysiloxane group include a divalent polysiloxane group represented by the following formula (i) or (ii), a monovalent polysiloxane group represented by the following formula (iii) or (iv), and a trivalent or higher polysiloxane group obtained by removing three or more organic groups bonded to silicon atoms constituting the skeleton of an organopolysiloxane. -(SiR 1b R 1c -O) n -SiR 1d R 1e - (i) -Si((OSiR 2b R 2c ) r -OSiR 2d R 2e R 2f)2-OSi((OSiR 2g R 2h ) s -OSiR 2i R 2j R 2k )2- (ii) -(SiR 3b R 3c -O) x -SiR 3d R 3e R 3f (iii) -Si(OSiR 4b R 4c R 4d )3···(iv)

[0031] In formula (i), n is 3 to 80; R 1b ~R 1e respectively represent an alkyl group, an alkoxy group, a phenyl group, a substituted phenyl group, a phenoxy group or a substituted phenoxy group. In formula (ii), r and s are each 0 to 20, R 2b ~R 2k Each represents an alkyl group. In formula (iii), x is 3 to 80; R 3b ~R 3f respectively represent an alkyl group, an alkoxy group, a phenyl group, a substituted phenyl group, a phenoxy group or a substituted phenoxy group. In formula (iv), R 4b ~R 4d are alkyl groups, -(OSiR 51 R 52 ) y -OSiR 53 R 54 R 55 (where y is an integer between 0 and 20, R 51 ~R 55 represents an alkyl group.) or R 56 -(OC2H4) y’ -OR 57 (where y' is an integer between 1 and 20, R 56 and R 57 Each represents an alkyl group.

[0032] In the above formula (i), n is the average degree of polymerization of the polysiloxane structure. If n is equal to or greater than the lower limit of the above range, the coating film of the antifouling coating composition containing the copolymer (X) tends to exhibit an antifouling effect even when the composition does not contain an antifouling agent, and if n is equal to or less than the upper limit of the above range, the monomer having the polysiloxane group is compatible with the monomer (a) and the like, and the solvent solubility of the resulting copolymer (X) is good. n is preferably 5 to 50, more preferably 8 to 40. R 1b ~R 1e The number of carbon atoms in the alkyl group and alkoxy group is preferably from 1 to 18. Examples of the substituent in the substituted phenyl group and the substituted phenoxy group include an alkyl group and an alkoxy group. R 1b ~R 1e are each preferably an alkyl group having 1 to 18 carbon atoms, more preferably a methyl group or an ethyl group, and particularly preferably a methyl group.

[0033] In the above formula (ii), r and s are each the average degree of polymerization of the polysiloxane structure. If r and s are each equal to or less than the upper limit, the monomer having the polysiloxane group is compatible with the monomer (a) and the like, and the resulting copolymer (X) has good solvent solubility. Each of r and s is preferably 10 or less, more preferably 5 or less. R 2b ~R 2k The alkyl group in is preferably an alkyl group having 1 to 18 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an n-butyl group, etc. Among these, a methyl group or an ethyl group is preferable, and a methyl group is particularly preferable.

[0034] In the above formula (iii), x is the average degree of polymerization of the polysiloxane structure. If x is equal to or greater than the lower limit of the above range, the coating film of the antifouling coating composition containing the copolymer (X) tends to exhibit an antifouling effect even when the composition does not contain an antifouling agent, and if x is equal to or less than the upper limit of the above range, the monomer having the polysiloxane group is compatible with the monomer (a) and the like, and the solvent solubility of the resulting copolymer (X) is good. x is preferably 5 to 50, more preferably 8 to 40. R3b ~R 3f The number of carbon atoms in the alkyl group and alkoxy group is preferably from 1 to 18. Examples of the substituent in the substituted phenyl group and the substituted phenoxy group include an alkyl group and an alkoxy group. R 3b ~R 3f are each preferably an alkyl group having 1 to 18 carbon atoms, more preferably a methyl group or an ethyl group, and particularly preferably a methyl group.

[0035] In the above formula (iv), R 4b ~R 4d The alkyl group in is preferably an alkyl group having 1 to 18 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an n-butyl group, etc. Among these, a methyl group or an ethyl group is preferable, and a methyl group is particularly preferable. y is the average degree of polymerization of the polysiloxane structure, and y' is the average degree of polymerization of the polyether structure. When y and y' are equal to or less than the upper limit, the monomer having the polysiloxane group is compatible with the monomer (a) and the like, and the resulting copolymer (X) has good solvent solubility. Each of y and y' is preferably 10 or less, more preferably 5 or less. R 51 ~R 57 The alkyl group in R 4b ~R 4d The alkyl groups in the above formula (I) are the same as those in the above formula (I), and preferred embodiments are also the same.

[0036] (Structural unit (B)) The structural unit (B) has a structure in which the ethylenically unsaturated bond of the monomer (b) is cleaved to form a single bond. The number of polysiloxane groups and ethylenically unsaturated bonds contained in the molecule of the monomer (b) is not particularly limited, and may be one or two or more. As the monomer (b), from the viewpoint of antifouling properties, a monomer having a divalent polysiloxane group and an ethylenically unsaturated bond-containing group bonded to each end of the group (hereinafter also referred to as a "double-ended polysiloxane macromonomer"), a monomer having a monovalent polysiloxane group and an ethylenically unsaturated bond-containing group bonded to one end of the group (hereinafter also referred to as a "single-ended polysiloxane macromonomer"), or a side-chain type polysiloxane macromonomer is preferred. Any of these may be used alone or in combination. Examples of the one-terminated polysiloxane macromonomer include monomers represented by the following formula (b1) or (b2). Examples of the double-terminated polysiloxane macromonomer include monomers represented by the following formula (b3) or (b4). An example of the side chain type polysiloxane macromonomer is a monomer represented by the following formula (b5). Therefore, the monomer (b) is preferably at least one selected from the group consisting of a monomer (b1) represented by the following formula (b1), a monomer (b2) represented by the following formula (b2), a monomer (b3) represented by the following formula (b3), a monomer (b4) represented by the following formula (b4), and a monomer (b5) represented by the following formula (b5).

[0037] CH2=CR 3a -CO-O-(C u H 2u -O) v -C w H 2w -(SiR 3b R 3c -O) x -SiR 3d R 3e R 3f (b1) CH2=CR 4a -CO-O-(C u’ H 2u’ -O) v’ -C w’ H 2w’ -Si(OSiR 4b R 4c R 4d )3···(b2) CH2=CR 2a-CO-O-(C k’ H 2k’ -O) l’ -C m’ H 2m’ -Si((OSiR 2b R 2c ) r -OSiR 2d R 2e R 2f )2-OSi((OSiR 2g R 2h ) s -OSiR 2i R 2j R 2k )2-C о’ H 2о’ -(OC p’ H 2p’ ) q’ -O-CO-CR 2l =CH2 (b3) CH2=CR 1a -CO-O-(C k H 2k -O) l -C m H 2m -(SiR 1b R 1c -O) n -SiR 1d R 1e -C о H 2о -(OC p H 2p ) q -O-CO-CR 1f =CH2 (b4)

[0038] [ka]

[0039] Here, R 3a represents a hydrogen atom or a methyl group, u represents an integer of 2 to 5, v represents a number of 0 to 50, w represents an integer of 2 to 5, x represents a number of 3 to 80, R 3b ~R 3f each independently represents an alkyl group, an alkoxy group, a phenyl group, a substituted phenyl group, a phenoxy group or a substituted phenoxy group, R4a represents a hydrogen atom or a methyl group, u' represents an integer of 2 to 5, v' represents a number of 0 to 50, w' represents an integer of 2 to 5, R 4b ~R 4d are each independently an alkyl group, -(OSiR 51 R 52 ) y -OSiR 53 R 54 R 55 (where y is an integer between 0 and 20, and R 51 ~R 55 represents an alkyl group.) or -R 56 -(OC2H4) y’ -OR 57 (where y' is an integer from 1 to 20, and R 56 represents an alkylene group, and R 57 represents an alkyl group; R 2a and R 2l each independently represents a hydrogen atom or a methyl group; k' and p' each independently represents an integer of 2 to 5; l' and q' each independently represents a number of 0 to 50; m' and o' each independently represents an integer of 2 to 5; r and s each independently represents a number of 0 to 20; R 2b ~R 2k each independently represents an alkyl group, R 1a and R 1f each independently represents a hydrogen atom or a methyl group, k and p each independently represents an integer of 2 to 5, l and q each independently represents a number of 0 to 50, m and o each independently represents an integer of 2 to 5, n represents a number of 3 to 80, R 1b ~R 1e each independently represents an alkyl group, an alkoxy group, a phenyl group, a substituted phenyl group, a phenoxy group or a substituted phenoxy group. In formula (b5), R 50 represents a hydrogen atom or a methyl group, a' represents an integer of 2 to 5, b' represents a number of 0 to 50, c' represents an integer of 0 to 18, d' represents a number of 1 to 1000, e' represents a number of 1 to 80, R 51 ~R 59respectively represent an alkyl group, an alkoxy group, a phenyl group, a substituted phenyl group, a phenoxy group or a substituted phenoxy group.

[0040] In the formula (b1), u represents an integer of 2 to 5, and from the viewpoint of cost, 2 or 3 is preferable. It is also possible to use a combination of u=2 and u=3. v is the average degree of polymerization of the polyether structure, and is a number from 0 to 50. If v is 50 or less, the water resistance of the coating film tends to be good. In particular, v being 30 or less is preferable because it provides excellent recoatability with a previous coating film. v may be 0, but is preferably greater than 0 because it tends to provide good recoatability with a previous coating film. v is preferably greater than 0 and not greater than 30, more preferably 3 to 25, and even more preferably 5 to 20. w represents an integer of 2 to 5, and is preferably 2 or 3. x is the average degree of polymerization of the polysiloxane structure, and is a number from 3 to 80. When x is equal to or more than the lower limit, even if the resin composition or coating composition containing the copolymer (X) does not contain an antifouling agent, the coating film tends to exhibit an antifouling effect, and when x is equal to or less than the upper limit, the monomer (b1) is compatible with the monomer (a) and the like, and the organic solvent solubility of the resulting copolymer (X) is good. x is preferably 5 to 50, more preferably 8 to 40. R 3b ~R 3f The number of carbon atoms in the alkyl group and alkoxy group is preferably from 1 to 18. Examples of the substituent in the substituted phenyl group and the substituted phenoxy group include an alkyl group and an alkoxy group. R 3b ~R 3f are each preferably an alkyl group having 1 to 18 carbon atoms, more preferably a methyl group or an ethyl group, and particularly preferably a methyl group. In addition, R 3a ~R 3f , u, v, w and x are each independent, and when the same symbol is present within or between molecules, they may be different.

[0041] Specific examples of the monomer (b1) include those having v of 0, such as FM-0711, FM-0721, and FM-0725 (all trade names) manufactured by JNC Corporation, and X-24-8201, X-22-174DX, and X-22-2426 (all trade names) manufactured by Shin-Etsu Chemical Co., Ltd. Specific examples of the monomer (b1) include those having v of 0, such as F2-254-04 and F2-254-14 (trade names) manufactured by Dow Corning Toray Co., Ltd. The monomer (b1) may be used alone or in combination of two or more kinds.

[0042] In formula (b2), u' is an integer of 2 to 5, and from the viewpoint of cost, u' is preferably 2 or 3. It is also possible to use u' of 2 and u' of 3 in combination. v' is the average degree of polymerization of the polyether structure and is a number from 0 to 50. If v' is 50 or less, the water resistance of the coating film tends to be good. In particular, it is preferable that v' is 30 or less, since the recoatability with the old coating film is excellent. v' may be 0, but since the recoatability with the old coating film tends to be good, it is preferable that v' is greater than 0. v' is preferably more than 0 and not more than 30, more preferably 3 to 25, and even more preferably 5 to 20. w' represents an integer of 2 to 5, and is preferably 2 or 3. R 4b ~R 4d The alkyl group in is preferably an alkyl group having 1 to 18 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an n-butyl group, etc. Among these, a methyl group or an ethyl group is preferable, and a methyl group is particularly preferable. y is the average degree of polymerization of the polysiloxane structure and is an integer of 0 to 20. y' is the average degree of polymerization of the polyether structure and is an integer of 1 to 20. When y and y' are not more than the upper limit values, the monomer (b2) is compatible with the monomer (a) and the like, and the organic solvent solubility of the resulting copolymer (X) is good. Each of y and y' is preferably 10 or less, more preferably 5 or less. R 51 ~R 55 , R 57 The alkyl group in R 4b ~R 4dThe same alkyl groups as those in the alkyl group in R are included, and the preferred embodiments are also the same. 56 In the above formula, the alkylene group preferably has 1 to 18 carbon atoms. In addition, R 4a ~R 4d , u', v', w', y and y' are each independent, and when the same symbol is present within or between molecules, they may be different.

[0043] Specific examples of the monomer (b2) include those having v' of 0, such as TM-0701 (trade name) manufactured by JNC Corporation, X-22-2404 (trade name) manufactured by Shin-Etsu Chemical Co., Ltd., and F2-250-01 and F2-302-01 (all trade names) manufactured by Dow Corning Toray Co., Ltd. Those having v' of more than 0, such as F2-302-04 (trade name) manufactured by Dow Corning Toray Co., Ltd. The monomer (b2) may be used alone or in combination of two or more kinds.

[0044] In formula (b3), k' and p' each represent an integer of 2 to 5, and from the viewpoint of cost, preferably 2 or 3. It is also possible to use k' and p' each having 2 and 3 in combination. l' and q' are the average polymerization degrees of the polyether structure and are numbers from 0 to 50. If l' and q' are 50 or less, the water resistance of the coating film tends to be good. In particular, it is preferable that they are 30 or less, since the recoatability with the old coating film is excellent. l' and q' may be 0, but since the recoatability with the old coating film tends to be good, it is preferable that they are greater than 0. l' and q' are preferably more than 0 and 30 or less, more preferably 3 to 25, and even more preferably 5 to 20. m' and o' each represent an integer of 2 to 5, with 2 or 3 being preferred. Each of r and s is an average degree of polymerization of the polysiloxane structure, and is a number from 0 to 20. When each of r and s is equal to or less than the upper limit, the monomer (b3) is compatible with the monomer (a) and the like, and the organic solvent solubility of the resulting copolymer (X) is good. Each of r and s is preferably equal to or less than 10, more preferably equal to or less than 5. R 2b ~R 2kThe alkyl group in is preferably an alkyl group having 1 to 18 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, or an n-butyl group. Among these, a methyl group or an ethyl group is preferred, and a methyl group is particularly preferred. In addition, R 2a ~R 2l , k', l', m', n', o', p', q', r and s are each independent, and when the same symbol is present within or between molecules, they may be different.

[0045] Specific examples of the monomer (b3) include F2-312-01 (product name) manufactured by Dow Corning Toray Co., Ltd., for example, one in which l' and q' are 0. Examples of the monomer (b3) include F2-312-04 (product name) manufactured by Dow Corning Toray Co., Ltd., for example, one in which l' and q' are greater than 0. The monomer (b3) may be used alone or in combination of two or more kinds.

[0046] In formula (b4), k and p each represent an integer of 2 to 5, and from the viewpoint of cost, are preferably 2 or 3. It is also possible to use k and p each having 2 and 3 in combination. l and q are the average polymerization degrees of the polyether structure and are numbers from 0 to 50. When l and q are 50 or less, the water resistance of the coating film tends to be good. In particular, it is preferable that l and q are 30 or less, since the recoatability with the old coating film is excellent. l and q may be 0, but since the recoatability with the old coating film tends to be good, it is preferable that they are greater than 0. l and q are preferably more than 0 and 30 or less, more preferably 3 to 25, and even more preferably 5 to 20. m and o each represent an integer of 2 to 5, with 2 or 3 being preferred. n is the average degree of polymerization of the polysiloxane structure, and is a number from 3 to 80. When n is equal to or more than the lower limit, even if the resin composition or coating composition containing the copolymer (X) does not contain an antifouling agent, the coating film tends to exhibit an antifouling effect, and when n is equal to or less than the upper limit, the monomer (b4) is compatible with the monomer (a) and the like, and the organic solvent solubility of the resulting copolymer (X) is good. n is preferably 5 to 50, more preferably 8 to 40. R 1b ~R 1e The number of carbon atoms in the alkyl group and alkoxy group is preferably from 1 to 18. Examples of the substituent in the substituted phenyl group and the substituted phenoxy group include an alkyl group and an alkoxy group. R 1b ~R 1e are each preferably an alkyl group having 1 to 18 carbon atoms, more preferably a methyl group or an ethyl group, and particularly preferably a methyl group. In addition, R 1a ~R 1f , k, l, m, n, o, p and q are each independent, and when the same symbol is present within or between molecules, they may be different.

[0047] Specific examples of the monomer (b4) include those in which l and q are 0, such as FM-7711, FM-7721, and FM-7725 (all trade names) manufactured by JNC Corporation, and F2-311-02 (trade name) manufactured by Dow Corning Toray Co., Ltd., etc. Examples of those in which l and q are greater than 0 include F2-354-04 (trade name) manufactured by Dow Corning Toray Co., Ltd., etc. The monomer (b4) may be used alone or in combination of two or more kinds.

[0048] In formula (b5), a′ is an integer of 2 to 5. In formula (b5), b' is a number from 0 to 50, and is preferably greater than 0 and not greater than 30, more preferably greater than 0 and not greater than 25, and particularly preferably greater than 0 and not greater than 20. When b' is equal to or less than the upper limit of the aforementioned range, the water resistance of the coating film tends to be good. In particular, it is preferable that b' is 20 or less, since the recoatability with the old coating film is excellent. In formula (b5), c' is an integer of 0 to 18, preferably 2 or 3, and more preferably 3. d' is an integer of 1 to 1000, preferably an integer of 1 to 200, and more preferably an integer of 1 to 100, and particularly preferably an integer of 1 to 60. If d' exceeds 1000, compatibility with other polymerizable monomers during synthesis of a polymer tends to be poor. When e' in formula (b5) is equal to or greater than the lower limit of the above range, the antifouling property tends to be better, and when it is equal to or less than the upper limit of the above range, the solvent solubility, wear resistance, and crack resistance tend to be better. In formula (b5), e' is preferably equal to or less than 80, more preferably equal to or less than 50, even more preferably equal to or less than 10, and particularly preferably equal to or less than 5. Furthermore, d'+e' is preferably from 2 to 1,000, and more preferably from 2 to 500.

[0049] From the viewpoint of the crack resistance of the coating film and adhesion to the substrate, it is preferable that the structural unit (B) consists only of structural units based on monomer (b1) or (b2), which contains an ethylenically unsaturated bond at one terminal of the monomer (b). From the standpoint of recoatability, the structural unit (B) preferably contains a structural unit based on the monomer (b1) or (b2) and a structural unit based on the monomer (b3) or (b4). From the standpoint of smoothness of the coating film, the structural unit (B) preferably contains a structural unit based on the monomer (b5).

[0050] When the structural unit (B) contains a structural unit based on monomer (b1) or (b2) and a structural unit based on monomer (b3) or (b4), the ratio (molar ratio) thereof is preferably 1 / 99 to 80 / 20, more preferably 3 / 97 to 60 / 40, i.e., structural unit based on monomer (b3) or (b4) / structural unit based on monomer (b1) or (b2). If the ratio of the structural unit based on monomer (b3) or (b4) is 80 / 20 or less, a coating film having excellent crack resistance and adhesion to the substrate tends to be obtained. If the ratio of the structural unit based on monomer (b3) or (b4) is 1 / 99 or more, the long-term antifouling property and recoatability of the coating film formed tend to be better.

[0051] (Structural unit (C)) The monomer (c) is a polymerizable monomer other than the monomer (a) and the monomer (b). The monomer (c) may be any monomer capable of copolymerizing with the monomer (a) and the monomer (b), and examples thereof include compounds containing an ethylenically unsaturated bond (excluding the monomer (a) and the monomer (b)).

[0052] Examples of the monomer (c) include the following: Substituted or unsubstituted alkyl (meth)acrylates [e.g., methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, 1-methyl-2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 3-methyl-3-methoxybutyl (meth)acrylate], substituted or unsubstituted aralkyl (meth)acrylates [e.g., benzyl ( hydrophobic group-containing (meth)acrylic acid ester monomers such as aryl (meth)acrylate, m-methoxyphenylethyl (meth)acrylate, p-methoxyphenylethyl (meth)acrylate, substituted or unsubstituted aryl (meth)acrylates [e.g., phenyl (meth)acrylate, m-methoxyphenyl (meth)acrylate, p-methoxyphenyl (meth)acrylate, o-methoxyphenylethyl (meth)acrylate], alicyclic (meth)acrylates [e.g., isobornyl (meth)acrylate, cyclohexyl (meth)acrylate], trifluoroethyl (meth)acrylate, perfluorooctyl (meth)acrylate, and perfluorocyclohexyl (meth)acrylate; oxyethylene group-containing (meth)acrylic acid ester monomers, such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, butoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxyethyl (meth)acrylate, and 2-(2-ethylhexaoxy)ethyl (meth)acrylate; hydroxyl group-containing (meth)acrylic acid ester monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and glycerol (meth)acrylate; terminal alkoxyallylated polyether monomers such as methoxy polyethylene glycol allyl ether, methoxy polypropylene glycol allyl ether, butoxy polyethylene glycol allyl ether, butoxy polypropylene glycol allyl ether, methoxy polyethylene glycol-polypropylene glycol allyl ether, and butoxy polyethylene glycol-polypropylene glycol allyl ether; Epoxy group-containing vinyl monomers such as glycidyl (meth)acrylate, α-ethyl glycidyl acrylate, and 3,4-epoxybutyl (meth)acrylate; Primary or secondary amino group-containing vinyl monomers such as butylaminoethyl (meth)acrylate and (meth)acrylamide; Tertiary amino group-containing vinyl monomers such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, dimethylaminobutyl (meth)acrylate, dibutylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylamide, and dimethylaminopropyl (meth)acrylamide; Heterocyclic basic monomers such as vinylpyrrolidone, vinylpyridine, and vinylcarbazole; Trimethylsilyl (meth)acrylate, triethylsilyl (meth)acrylate, tri-n-propylsilyl (meth)acrylate, tri-n-butylsilyl (meth)acrylate, tri-n-amylsilyl (meth)acrylate, tri-n-hexylsilyl (meth)acrylate, tri-n-octylsilyl (meth)acrylate, tri-n-dodecylsilyl (meth)acrylate, triphenylsilyl (meth)acrylate, tri-p-methylphenylsilyl (meth)acrylate, tribenzylsilyl (meth)acrylate, triisopropylsilyl (meth)acrylate, triisobutylsilyl (meth)acrylate, tri-s-butylsilyl (meth)acrylate, tri-2-methylisopropylsilyl (meth)acrylate, tri-t-butylsilyl (meth)acrylate, ethyldimethylsilyl (meth)acrylate, n-butyldimethylsilyl (meth) Organosilyl group-containing vinyl monomers such as acrylate, diisopropyl-n-butylsilyl (meth)acrylate, n-octyldi-n-butylsilyl (meth)acrylate, diisopropylstearylsilyl (meth)acrylate, dicyclohexylphenylsilyl (meth)acrylate, t-butyldiphenylsilyl (meth)acrylate, lauryldiphenylsilyl (meth)acrylate, triisopropylsilylmethyl maleate, triisopropylsilylamyl maleate, tri-n-butylsilyl-n-butyl maleate, t-butyldiphenylsilylmethyl maleate, t-butyldiphenylsilyl-n-butyl maleate, triisopropylsilylmethyl fumarate, triisopropylsilylamyl fumarate, tri-n-butylsilyl-n-butyl fumarate, t-butyldiphenylsilylmethyl fumarate, and t-butyldiphenylsilyl-n-butyl fumarate; Vinyl monomers containing an acid anhydride group, such as maleic anhydride and itaconic anhydride; Methacrylic acid, acrylic acid, crotonic acid, vinylbenzoic acid, fumaric acid, itaconic acid, maleic acid, citraconic acid, monomethyl maleate, monoethyl maleate, monobutyl maleate, monooctyl maleate, monomethyl itaconate, monoethyl itaconate, monobutyl itaconate, monooctyl itaconate, monomethyl fumarate, monoethyl fumarate, monobutyl fumarate, monooctyl fumarate, monoethyl citraconic acid, monohydroxyethyl tetrahydrophthalate (meth)acrylate, tetrahydrophthalic acid Carboxy group-containing ethylenically unsaturated monomers such as monohydroxypropyl phthalate (meth)acrylate, monohydroxybutyl tetrahydrophthalate (meth)acrylate, monohydroxyethyl phthalate (meth)acrylate, monohydroxypropyl phthalate (meth)acrylate, monohydroxyethyl succinate (meth)acrylate, monohydroxypropyl succinate (meth)acrylate, monohydroxyethyl maleate (meth)acrylate, and monohydroxypropyl maleate (meth)acrylate; Unsaturated dicarboxylic acid diester monomers such as dimethyl malate, dibutyl malate, dimethyl fumarate, dibutyl fumarate, dibutyl itaconate, and diperfluorocyclohexyl fumarate; Cyano group-containing vinyl monomers such as acrylonitrile and methacrylonitrile; vinyl ether monomers such as alkyl vinyl ethers [e.g., ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, hexyl vinyl ether, 2-ethylhexyl vinyl ether, etc.] and cycloalkyl vinyl ethers [e.g., cyclohexyl vinyl ether, etc.]; Vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl butyrate, and vinyl benzoate; Aromatic vinyl monomers such as styrene, vinyl toluene, and α-methyl styrene; Halogenated olefins such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride, and chlorotrifluoroethylene; Polyfunctional monomers such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl methacrylate, triallyl cyanurate, diallyl maleate, and polypropylene glycol diallyl ether; macromonomers, and the like.

[0053] The macromonomer (c) may be a compound having an ethylenically unsaturated bond-containing group and having two or more structural units derived from a monomer having an ethylenically unsaturated bond-containing group. The two or more structural units of the macromonomer may be the same or different. Examples of the ethylenically unsaturated bond-containing group include CH2=C(COOR)-CH2-, (meth)acryloyl group, 2-(hydroxymethyl)acryloyl group, vinyl group, etc. Here, R represents a hydrogen atom, an unsubstituted or substituted alkyl group, an unsubstituted or substituted alicyclic group, an unsubstituted or substituted aryl group, or an unsubstituted or substituted heterocyclic group. Examples of the substituent include an alkyl group (excluding the case where R is an alkyl group having a substituent), an aryl group, -COOR 61 , cyano group, -OR 62 , -NR 63 R 64 , -CONR 65 R 66 , a halogen atom, an allyl group, an epoxy group, a siloxy group, and a group exhibiting hydrophilicity or ionicity. 61 ~R 66 each independently represents a hydrogen atom, an alkyl group, an alicyclic group, or an aryl group. As the monomer having an ethylenically unsaturated bond-containing group, for example, the various monomers given above as examples of the monomer (c) can be used (however, macromonomers are excluded). Specific examples of the macromonomer include those disclosed in WO 2013 / 108880.

[0054] One or more of these monomers (c) can be appropriately selected and used as required. The monomer (c) is preferably a monofunctional monomer having one ethylenically unsaturated bond, and more preferably the ethylenically unsaturated bond is derived from an acryloyl group, because it is easy to obtain a low viscosity even with a high solid content when the copolymer (X) is dissolved in an organic solvent. That is, the monomer (c) is particularly preferably a monofunctional monomer having one acryloyl group.

[0055] It is preferable that the structural unit (C) contains a structural unit based on a hydrophobic group-containing (meth)acrylic acid ester monomer, in that this allows for a good balance between the flexibility, crack resistance or peel resistance, and the long-term self-polishing properties of the coating film to be formed. As the hydrophobic group-containing (meth)acrylic acid ester monomer, alkyl (meth)acrylate is preferred.

[0056] From the standpoint of the solubility and crack resistance of the coating film to be formed, the structural unit (C) preferably contains a structural unit based on an oxyethylene group-containing (meth)acrylic acid ester monomer. As the oxyethylene group-containing (meth)acrylic acid ester monomer, a compound represented by the following formula (3-1) is preferred. Z 1 -(CH2CH2O) t R 21 (3-1) (Here, Z 1 represents an acryloyloxy group or a methacryloyloxy group, R 21 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group, and t represents an integer of 1 to 15.

[0057] In formula (3-1), Z 1 When the acrylic acid group is an acryloyloxy group, the hydrolysis rate tends to be faster than that when the acrylic acid group is a methacryloyloxy group, and the acrylic acid group can be selected arbitrarily according to the dissolution rate. R 21 In the above formula, examples of the alkyl group having 1 to 10 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, a hexyl group, and a 2-ethylhexyl group. The number of carbon atoms in the alkyl group is preferably 1 to 4, more preferably 1 to 3, and further preferably 1 or 2. The aryl group is preferably an aryl group having 6 to 20 carbon atoms, and examples of the aryl group include a phenyl group and a naphthyl group. From the viewpoints of water resistance and crack resistance, t is preferably an integer of 1 to 10, more preferably an integer of 1 to 5, further preferably an integer of 1 to 3, and particularly preferably 1 or 2.

[0058] (Content of each constituent unit) The content of the structural unit (A) is preferably 2 to 35% by mass, more preferably 4 to 30% by mass, and even more preferably 8 to 25% by mass, based on the total mass (100% by mass) of all structural units constituting the copolymer (X). If the content of the structural unit (A) is equal to or greater than the lower limit, the coating film formed will have better self-polishing properties. If the content of the structural unit (A) is equal to or less than the upper limit, the coating film formed will have better crack resistance, will maintain its self-polishing properties for a long period of time, and will have better antifouling effects.

[0059] The content of the structural unit (B) is preferably 15 to 75% by mass, more preferably 20 to 70% by mass, and even more preferably 25 to 65% by mass, based on the total mass of all structural units constituting the copolymer (X). If the content of the structural unit (B) is equal to or greater than the lower limit, the coating film formed has excellent antifouling properties even without the use of an antifouling agent. If the content of the structural unit (B) is equal to or less than the upper limit, the coating film formed has excellent crack resistance, maintains self-polishing properties for a long period of time, and has a more excellent antifouling effect.

[0060] The total content of the structural units (B) based on monomer (b3) and the structural units based on monomer (b4) is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the total mass of all structural units constituting copolymer (X). If the total content of the structural units based on monomer (b3) and the structural units based on monomer (b4) is less than the upper limit, the copolymer (X) tends to be obtained without gelation due to crosslinking during production. In addition, the viscosity of the solution of copolymer (X) tends to be low.

[0061] The total content of the structural units (A) and (B) is preferably 20 to 90 mass%, more preferably 30 to 85 mass%, and even more preferably 40 to 80 mass%, based on the total mass of all structural units constituting the copolymer (X). The content of the structural unit (C) is preferably from 10 to 80 mass%, more preferably from 15 to 70 mass%, and even more preferably from 20 to 60 mass%, based on the total mass of all structural units constituting the copolymer (X).

[0062] When the structural unit (C) contains a structural unit based on an oxyethylene group-containing (meth)acrylic acid ester monomer, the content of this structural unit is preferably 1 to 60 mass%, more preferably 5 to 55 mass%, and even more preferably 10 to 50 mass%, based on the total mass of all structural units constituting the copolymer (X). If the content of this structural unit is equal to or greater than the lower limit, the coating film formed will have higher hydrophilicity and better self-polishing properties. If the content of this structural unit is equal to or less than the upper limit, the coating film formed will have appropriate hydrolysis properties, will maintain self-polishing properties for a long period of time, and will have better antifouling effects.

[0063] When the structural unit (C) contains a structural unit based on a monomer (c) other than an oxyethylene group-containing (meth)acrylic acid ester monomer, such as a hydrophobic group-containing (meth)acrylic acid ester monomer, the content of this structural unit is preferably 1 to 60 mass%, more preferably 5 to 55 mass%, based on the total mass of all structural units constituting the copolymer (X). If the content of this structural unit is within the above range, the flexibility, crack resistance, and peel resistance of the coating film formed will be higher, and the antifouling effect will be better. In addition, if the content of this structural unit is equal to or less than the upper limit, the coating film formed will have appropriate hydrolysis properties, maintain self-polishing properties for a long period of time, and have a better antifouling effect.

[0064] The total of the structural units (A), (B) and (C) is 100% by mass. The content (mass %) of each structural unit in the copolymer can be measured by a known method such as gas chromatography, high performance liquid chromatography, or nuclear magnetic resonance spectroscopy.

[0065] At least a portion of the structural units constituting the copolymer (X) is preferably a structural unit based on a (meth)acrylic monomer. The content of the structural units based on the (meth)acrylic monomer is preferably from 20 to 100 mass %, and more preferably from 40 to 100 mass %, based on the total mass of all the structural units constituting the copolymer (X). It is preferable that the above-mentioned monomers (b1) to (b5) are all (meth)acrylic monomers, and the structural unit (B) is a structural unit based on a (meth)acrylic monomer. The above-mentioned monomers (a1) and (a2) are both (meth)acrylic monomers, and when the structural unit (A) is a structural unit based on the monomer (a1) or (a2), the structural unit (A) is also a structural unit based on a (meth)acrylic monomer. When the copolymer (X) contains the structural unit (C), the structural unit (C) may or may not contain a structural unit based on a (meth)acrylic monomer.

[0066] The copolymer (X) is preferably a copolymer obtained by polymerizing a monomer mixture containing a monomer (a) and a monomer (b). Such a copolymer tends to have better water resistance than a copolymer obtained by polymerizing a monomer mixture containing a monomer (a0) having an ethylenically unsaturated bond and a carboxyl group and a monomer (b) to obtain a copolymer (X0) having a carboxyl group, and converting the carboxyl group of this copolymer (X0) to structure (I). The monomer mixture preferably contains 2 to 35% by mass of monomer (a) and 15 to 75% by mass of monomer (b). The monomer mixture preferably contains 2 to 35% by mass of monomer (a), 15 to 75% by mass of monomer (b), and 10 to 80% by mass of monomer (c). The content of each monomer is a ratio to the total amount of the monomer mixture. The more preferred range of the content of each monomer is the same as the preferred range of the content of the constituent unit based on each monomer.

[0067] The weight-average molecular weight of the copolymer (X) is preferably 1,000 to 100,000, more preferably 2,000 to 80,000, and even more preferably 3,000 to 60,000. When the weight-average molecular weight is equal to or less than the upper limit of the above range, the viscosity of a solution in which the copolymer (X) is dissolved in a solvent is lower, and it is easy to obtain an antifouling coating composition with a high solid content and low viscosity. In addition, the antifouling properties of the coating film formed are excellent. When the weight-average molecular weight is equal to or more than the lower limit of the above range, the hardness and durability of the coating film formed are excellent.

[0068] The number average molecular weight (Mn) of the copolymer (X) is preferably from 500 to 50,000, more preferably from 1,000 to 40,000. The molecular weight distribution (Mw / Mn) of the copolymer (X) is preferably from 1.5 to 5.0, more preferably from 2.2 to 3.0. The weight average molecular weight and number average molecular weight of the copolymer (X) are each measured by gel permeation chromatography (GPC) using polystyrene as a standard resin.

[0069] (Method for producing copolymer (X)) Examples of the production method of the copolymer (X) include the following production methods (α) and (β). Production method (α): A method of polymerizing a monomer mixture containing monomer (a) and monomer (b). Production method (β): A method of polymerizing a monomer mixture containing a monomer (a0) having an ethylenically unsaturated bond and a carboxy group, and a monomer (b) to obtain a copolymer (X0) having a carboxy group, and converting the carboxy group of this copolymer (X0) to the structure (I).

[0070] "Manufacturing method (α)": In the production method (α), a monomer mixture containing a monomer (a) and a monomer (b) (hereinafter also referred to as "monomer mixture (α1)") is polymerized. The monomer mixture (α1) may further contain a monomer (c).

[0071] The composition of the monomer mixture (α1), i.e., the type of monomer constituting the monomer mixture (α1) and the content (% by mass) of each monomer relative to the total mass of all monomers, is similar to the composition of the copolymer (X), i.e., the type of monomer forming each structural unit constituting the copolymer (X) and the content (% by mass) of each structural unit relative to the total mass of all structural units.

[0072] The monomer mixture (α1) can be polymerized by known polymerization methods such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. From the viewpoints of productivity and coating film performance, the solution polymerization is preferred. The polymerization may be carried out by a known method using a known polymerization initiator. For example, a method may be used in which the monomer mixture (α1) is reacted in the presence of a radical initiator at a reaction temperature of 60 to 120° C. for 4 to 14 hours. During the polymerization, a chain transfer agent may be used as necessary.

[0073] As the radical initiator, known ones can be used, and examples thereof include 2,2-azobisisobutyronitrile, 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(2-methylbutyronitrile), benzoyl peroxide, cumene hydroperoxide, lauryl peroxide, di-t-butyl peroxide, and t-butylperoxy-2-ethylhexanoate. The content of the polymerization initiator is not particularly limited and can be appropriately set, and is typically about 0.1 to 20 parts by mass with respect to 100 parts by mass of the polymerizable monomer.

[0074] As the chain transfer agent, known ones can be used, and examples thereof include mercaptans such as n-dodecyl mercaptan, thioglycolic acid esters such as octyl thioglycolate, α-methylstyrene dimer, terpinolene, and the like. The content of the chain transfer agent is not particularly limited and can be appropriately set, and is typically about 0.0001 to 10 parts by mass relative to 100 parts by mass of the polymerizable monomer.

[0075] As the solvent used in the solution polymerization, for example, a general organic solvent such as toluene, xylene, methyl isobutyl ketone, or n-butyl acetate can be used.

[0076] "Manufacturing method (β)": In the production method (β), a monomer mixture containing a monomer (a0) and a monomer (b) (hereinafter also referred to as "monomer mixture (β1)") is polymerized to obtain a copolymer (X0) having a carboxy group, and the carboxy group of this copolymer (X0) is converted to a structure (I). The monomer mixture (β1) may further contain a monomer (c).

[0077] The composition of the monomer mixture (β1) is the same as that of the monomer mixture (α1) except that the monomer (a) is the monomer (a0). Examples of the monomer (m0) include (meth)acrylic acid, crotonic acid, isocrotonic acid, maleic acid, fumaric acid, itaconic acid, monomethyl maleate, and monomethyl fumarate. The polymerization of the monomer mixture (β1) can be carried out in the same manner as the polymerization of the monomer mixture (α1) in the production method (α).

[0078] An example of a method for converting the carboxy group of the copolymer (X0) to a structure represented by formula (1) is to react the copolymer (X0) with a metal oxide such as zinc oxide. As a method for converting the carboxy group of the copolymer (X0) into the structure represented by formula (2), for example, a method for converting the copolymer (X0) into the structure represented by formula (21) may be used. 32 (That is, R in Equation (2) 0 ) is reacted with a metal oxide such as zinc oxide. The metal of the metal oxide corresponds to M in the above formulas (1) and (2). The reaction of the copolymer (X0) with a metal oxide, or the reaction of the copolymer (X0) with an organic acid and a metal oxide can be carried out, for example, by raising the temperature to the reflux temperature, removing the mixture of the organic acid, water and organic solvent that is distilled off, and replenishing the same amount of organic solvent while continuing the reaction for 10 to 20 hours.

[0079] <Copolymer (Y)> The copolymer (Y) has a hydrolyzable group. The hydrolyzable group is preferably at least one group selected from structure (I) represented by the following formula (1) or (2), a triorganosilyloxycarbonyl group, or at least one group selected from structure (II) represented by the following formula (3), (4), or (5). Among them, structure (I) is preferred from the viewpoint of storage stability. The following formula (1), formula (2) and structure (I) are the same as the formula (1), formula (2) and structure (I) explained in the copolymer (X). -CO-OMO-CO- ···(1) -CO-OMR 0 (2) Here, M represents Zn, Cu, Mg, or Ca, and R 0 represents a monovalent organic acid residue.

[0080] [ka]

[0081] In the formulas (3) to (5), X is -O-, -S- or -NR 13 - indicates R 13 represents a hydrogen atom or an alkyl group, R 1’ and R 2’ each represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 3’ and R 5’ each represents an alkyl group, a cycloalkyl group, or an aryl group having 1 to 20 carbon atoms; R 4’ and R 6’ Each represents an alkylene group having 1 to 10 carbon atoms.

[0082] The copolymer (Y) may have one or more types of structure (I), triorganosilyloxycarbonyl group, and structure (II). The structure (I), the triorganosilyloxycarbonyl group, and the structure (II) may be contained in the structural unit of the copolymer (Y), may be contained in the main chain terminal, or may be contained in both. From the viewpoint of antifouling properties, it is preferable that they are contained in at least the structural unit. When Structure (I), the triorganosilyloxycarbonyl group, and Structure (II) are each contained in a structural unit, it is preferable that Structure (I), the triorganosilyloxycarbonyl group, and Structure (II) are contained in different structural units.

[0083] The copolymer (Y) preferably has at least one structural unit selected from the group consisting of a structural unit (yA1) based on a metal atom-containing polymerizable monomer (ya1) (hereinafter also referred to as "monomer (ya1)") having a structure (I) and an ethylenically unsaturated bond (polymerizable carbon-carbon double bond), a structural unit (yA2) based on a polymerizable monomer (ya2) (hereinafter also referred to as "monomer (ya2)") having a triorganosilyloxycarbonyl group and an ethylenically unsaturated bond (polymerizable carbon-carbon double bond), and a structural unit (yA3) based on a polymerizable monomer (ya3) (hereinafter also referred to as "monomer (ya3)") having a structure (II) and an ethylenically unsaturated bond (polymerizable carbon-carbon double bond). The monomer (ya1) is the same as the monomer (a) described in the copolymer (X). The structural unit (yA1) is the same as the structural unit (A) described in the copolymer (X). The copolymer (Y) may contain, as necessary, a structural unit (B) based on the monomer (b) described in the copolymer (X). The copolymer (Y) may contain other structural units based on other monomers other than the structural unit having a hydrolyzable group and the structural unit (B). The other structural units may be one or more types selected from the structural units (C) based on the monomer (c) explained in the copolymer (X). The copolymer (Y) is preferably a (meth)acrylic copolymer.

[0084] (structural unit yA1) The monomer (ya1) contains a structure (I) represented by the following formula (1) or (2) and an ethylenically unsaturated bond (polymerizable carbon-carbon double bond). -CO-OMO-CO- ···(1) -CO-OMR 0 (2) Here, M represents Zn, Cu, Mg, or Ca, and R 0 represents a monovalent organic acid residue.

[0085] The monomer (ya1) is preferably the monomer (a1) or the monomer (a2) described in the copolymer (X). The copolymer (Y) may contain a structural unit based on the monomer (a1) and a structural unit based on the monomer (a2).

[0086] (structural unit yA2) Examples of the structural unit (yA2) include a structural unit derived from a polymerizable monomer (ya2) having a triorganosilyloxycarbonyl group. The polymerizable monomer (ya2) typically has a triorganosilyloxycarbonyl group and an ethylenically unsaturated bond (polymerizable carbon-carbon double bond). The polymerizable monomer (ya2) is preferably a monofunctional monomer having one ethylenically unsaturated bond, since this reduces the viscosity of the copolymer (Y) when it is dissolved in an organic solvent.

[0087] Examples of the polymerizable monomer (ya2) include a monomer represented by the following formula (a21) and a monomer represented by the following formula (a22). Among these, the compound represented by the formula (a21) is preferred. CH2=C(R 17 )-CO-O-SiR 14 R 15 R 16 (a21) CH(COOR 18 )=C(R 17 )-CO-O-SiR 14 R 15 R 16 (a22) (In formulas (a21) and (a22), R 14 ~R 16 is an alkyl group having 1 to 20 carbon atoms, and R 17 represents a hydrogen atom or a methyl group, R 18 represents an alkyl group.)

[0088] Specific examples of the monomer represented by the formula (a21) include the following. Trimethylsilyl (meth)acrylate, triethylsilyl (meth)acrylate, tri-n-propylsilyl (meth)acrylate, tri-n-butylsilyl (meth)acrylate, tri-n-amylsilyl (meth)acrylate, tri-n-hexylsilyl (meth)acrylate, tri-n-octylsilyl (meth)acrylate, tri-n-dodecylsilyl (meth)acrylate, triphenylsilyl (meth)acrylate, tri-p-methylphenylsilyl (meth)acrylate, tribenzylsilyl (meth)acrylate, triisopropylsilyl (meth)acrylate, triisobutylsilyl (meth)acrylate Acrylate, tri-s-butylsilyl (meth)acrylate, tri-2-methylisopropylsilyl (meth)acrylate, tri-t-butylsilyl (meth)acrylate, ethyldimethylsilyl (meth)acrylate, n-butyldimethylsilyl (meth)acrylate, diisopropyl-n-butylsilyl (meth)acrylate, n-octyldi-n-butylsilyl (meth)acrylate, diisopropylstearylsilyl (meth)acrylate, dicyclohexylphenylsilyl (meth)acrylate, t-butyldiphenylsilyl (meth)acrylate, lauryldiphenylsilyl (meth)acrylate, and the like.

[0089] In the formula (a22), R 18 The alkyl group in the formula (I) may, for example, be an alkyl group having 1 to 5 carbon atoms. Specific examples of the compound represented by the formula (a22) include the following. Triisopropylsilyl methyl maleate, triisopropylsilyl amyl maleate, tri-n-butylsilyl-n-butyl maleate, t-butyldiphenylsilyl methyl maleate, t-butyldiphenylsilyl-n-butyl maleate, triisopropylsilyl methyl fumarate, triisopropylsilyl amyl fumarate, tri-n-butylsilyl-n-butyl fumarate, t-butyldiphenylsilyl methyl fumarate, t-butyldiphenylsilyl-n-butyl fumarate and the like. The polymerizable monomer (ya2) can be purchased as a commercially available product, or can be appropriately synthesized using a known method.

[0090] (structural unit yA3) An example of the structural unit (yA3) is a structural unit derived from a polymerizable monomer (ya3) having a structure (II). The polymerizable monomer (ya3) typically has at least one type of structure (II) and an ethylenically unsaturated bond (polymerizable carbon-carbon double bond). Structure (II) is represented by the following formula (3), formula (4), or formula (5): In each formula, among the single lines extending from the carbon atom of the carbonyl group, the line that is not bonded to the oxygen atom represents a bond.

[0091] [ka]

[0092] In the formulas (3) to (5), X is -O- (an ether oxygen atom), -S- (a sulfide sulfur atom), -NR 13 -, with -O- being preferred.

[0093] The polymerizable monomer (ya3) is preferably a monofunctional monomer having one ethylenically unsaturated bond, since this reduces the viscosity of the copolymer (Y) when it is dissolved in an organic solvent. Examples of the polymerizable monomer (ya3) include a compound represented by the following formula (a31), a compound represented by the following formula (a32), and a compound represented by the following formula (a33).

[0094] [ka]

[0095] (In formulas (a31) to (a33), Z is CH2=CH-COO-, CH2=C(CH3)-COO-, CHR X =CH-COO-, CH2=C(CH2R X )-COO- or CH2=CR X -CH2COO-, R Xrepresents the above structure (II) or an alkyl ester group, and X is -O-, -S-, or -NR 13 - indicates R 13 represents a hydrogen atom or an alkyl group, R 1’ ~R 6’ has the same meaning as above.)

[0096] In the formulae (a31) to (a33), in Z, CH2=CH-COO- is an acryloyloxy group, and CH2=C(CH3)-COO- is a methacryloyloxy group. CH(CH3)=CH-COO- is a crotonoyloxy group (the ethylenically unsaturated bond is in the trans form) or an isocrotonoyloxy group (the ethylenically unsaturated bond is in the cis form). CHR X =CH-COO- is a maleinoyloxy group (ethylenically unsaturated bond is in cis form) or a fumaroyloxy group (ethylenically unsaturated bond is in trans form) in which the carboxy group is substituted with structure (II) or an alkyl ester group. In formulas (a31) to (a33), R X The structure (II) in R X It is preferable that R has the same structure as the group to which Z is bonded. For example, in the case of a compound represented by formula (a31), R X -CR 1’ R 2’ -OR 3’ It is preferable that the group is represented by the following formula: In formulas (a31) to (a33), R X The alkyl ester group in X1 It is expressed as R X1 R represents an alkyl group. X1 The alkyl group is preferably an alkyl group having 1 to 6 carbon atoms, and a methyl group is particularly preferable. CH2=C(CH2R X )-COO- or CH2=CR X -CH2COO- is an itaconoyloxy group in which the carboxy group is substituted with structure (II) or an alkyl ester group. X is the same as above. In the formulas (a31) to (a33), Z is preferably CH2=CH-COO- or CH(CH3)=CH-COO-.

[0097] Specific examples of the polymerizable monomer (ya3) include the following.

[0098] [ka]

[0099] The polymerizable monomer (ya3) can be purchased as a commercially available product, or can be appropriately synthesized using a known method.

[0100] (Content of each constituent unit) In copolymer (Y), the content of the structural unit having a hydrolyzable group is preferably an amount such that the acid value of copolymer (Y) is 20 mgKOH / g or more, based on the total mass (100 mass%) of all structural units constituting copolymer (Y), more preferably 40 mgKOH / g or more, even more preferably 60 mgKOH / g or more, and particularly preferably 70 mgKOH / g or more, from the viewpoint of compatibility with copolymer (X).

[0101] In copolymer (Y), the total content of the structural units (yA1), (yA2), and (yA3), relative to the total mass (100 mass%) of all structural units constituting copolymer (Y), is preferably an amount such that the acid value of copolymer (Y) is 20 mgKOH / g or more, more preferably 40 mgKOH / g or more, even more preferably 60 mgKOH / g or more, and particularly preferably 70 mgKOH / g or more, from the viewpoint of compatibility with copolymer (X).

[0102] In the copolymer (Y), the content of the structural unit (B) is preferably 0 to 10 mass% based on the total mass of all structural units constituting the copolymer (Y). When the content of the structural unit (B) is equal to or less than the upper limit, the coating film formed has excellent crack resistance.

[0103] The total content of the structural units (B) based on monomer (b3) and the structural units based on monomer (b4) is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the total mass of all structural units constituting copolymer (Y). If the total content of the structural units based on monomer (b3) and the structural units based on monomer (b4) is less than the upper limit, the copolymer (Y) tends to be obtained without gelation due to crosslinking during production. In addition, the viscosity of the solution of copolymer (Y) tends to be low.

[0104] In the copolymer (Y), the total content of the structural unit having a hydrolyzable group and the structural unit (B) is preferably 2 to 60 mass%, more preferably 3 to 50 mass%, and even more preferably 5 to 40 mass%, based on the total mass of all the structural units constituting the copolymer (Y).

[0105] In the copolymer (Y), the total content of the structural units (yA1), (yA2), and (yA3) and the structural unit (B) is preferably 2 to 60 mass%, more preferably 3 to 50 mass%, and even more preferably 5 to 40 mass%, based on the total mass of all structural units constituting the copolymer (Y).

[0106] In the copolymer (Y), the content of the structural unit (C) is preferably 40 to 98 mass%, more preferably 50 to 97 mass%, and even more preferably 60 to 95 mass%, based on the total mass of all structural units constituting the copolymer (Y).

[0107] At least a portion of the structural units constituting the copolymer (Y) is preferably a structural unit based on a (meth)acrylic monomer. The content of the structural units based on the (meth)acrylic monomer is preferably from 20 to 100 mass %, and more preferably from 40 to 100 mass %, based on the total mass of all the structural units constituting the copolymer (Y).

[0108] The weight-average molecular weight of the copolymer (Y) is preferably 1,000 to 100,000, more preferably 2,000 to 80,000, and even more preferably 3,000 to 60,000. When the weight-average molecular weight is equal to or less than the upper limit of the above range, the viscosity of a solution in which the copolymer (Y) is dissolved in a solvent becomes lower, and it is easy to obtain an antifouling coating composition having a high solid content and low viscosity. When the weight-average molecular weight is equal to or more than the lower limit of the above range, the hardness and durability of the coating film formed are superior.

[0109] The number average molecular weight (Mn) of the copolymer (Y) is preferably from 500 to 50,000, more preferably from 1,000 to 40,000. The molecular weight distribution (Mw / Mn) of the copolymer (Y) is preferably from 1.5 to 5.0, more preferably from 2.2 to 3.0. The weight average molecular weight and number average molecular weight of the copolymer (Y) are each measured by gel permeation chromatography (GPC) using polystyrene as a standard resin.

[0110] (Method for producing copolymer (Y)) The copolymer (Y) can be produced by selecting a monomer appropriate for the structural unit and by a method similar to the above-mentioned method for producing the copolymer (X).

[0111] <Organic solvent> When the resin composition contains an organic solvent, the coating suitability of a coating composition containing the resin composition, the water resistance of the coating film formed, the film formability, etc. are improved. The organic solvent is not particularly limited, and a general organic solvent can be used, for example, a hydrocarbon solvent such as toluene or xylene, an ether solvent such as propylene glycol monomethyl ether-2-acetate, a ketone solvent such as methyl isobutyl ketone, an ester solvent such as n-butyl acetate, etc. Any one of these can be used alone, or two or more can be used in combination.

[0112] <Other ingredients> As the other components other than the copolymer (X), the copolymer (Y) and the organic solvent, for example, the other components listed in the coating composition described below can be used. However, the other components are not limited thereto, and can be appropriately selected from various known additives depending on the application of the resin composition. The resin composition can be used, for example, as a coating composition.

[0113] In the resin composition, the content ratio of the copolymer (X) to the copolymer (Y) is preferably from 95 / 5 to 40 / 60, more preferably from 90 / 10 to 45 / 55, in terms of mass ratio (X / Y). When the copolymer (Y) is contained in an amount equal to or more than the lower limit, the storage stability of the resin composition and the hardness of the coating film tend to be good, and when the copolymer (Y) is contained in an amount equal to or less than the upper limit, the antifouling properties of the coating film tend to be good.

[0114] The content of the structural unit (B) is preferably 15% by mass or more, more preferably 20% by mass or more, and particularly preferably 25% by mass or more, based on the total mass of all structural units of the copolymer (X) and the copolymer (Y). When the content of the structural unit (B) is equal to or more than the lower limit, the antifouling properties are good. The content of the structural unit (B) is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, based on the total mass of all structural units of the copolymer (X) and the copolymer (Y). If the content of the structural unit (B) is equal to or less than the upper limit, the crack resistance of the coating film is good.

[0115] In the resin composition, the total content of copolymer (X) and copolymer (Y) is preferably 35% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more, based on the total mass of the resin composition. If the total content of copolymer (X) and copolymer (Y) is equal to or more than the lower limit, a coating composition with a low VOC content can be easily obtained. The total content of copolymer (X) and copolymer (Y) is preferably an amount such that the viscosity of the resin composition measured at 25°C with a Gardner bubble viscometer is equal to or less than the preferred upper limit value described below. Although this varies depending on the weight average molecular weights, glass transition temperatures, and the presence or absence of crosslinked structures of copolymer (X) and copolymer (Y), the total content is preferably 85% by mass or less, and more preferably 80% by mass or less.

[0116] The content of the organic solvent relative to the total mass of the resin composition is preferably 65% ​​by mass or less, more preferably 60% by mass or less, and even more preferably 55% by mass or less, relative to the total mass of the resin composition. If the content of the organic solvent is equal to or less than the upper limit, a coating composition with a low VOC content can be easily obtained. The content of the organic solvent relative to the total mass of the resin composition is preferably an amount such that the viscosity of the resin composition measured at 25°C with a Gardner bubble viscometer is equal to or less than a preferred upper limit value described below. Although it varies depending on the weight average molecular weight, glass transition temperature, and the presence or absence of a crosslinked structure of the copolymer (X), the content is preferably 15 mass% or more, and more preferably 20 mass% or more, relative to the total mass of the resin composition.

[0117] The solid content (heating residue) of the resin composition is preferably 35% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more, based on the total mass of the resin composition. If the solid content is equal to or more than the lower limit, a coating composition with a low VOC content can be easily obtained. The solid content of the resin composition is preferably 85% by mass or less, and more preferably 80% by mass or less, based on the total mass of the resin composition, from the viewpoint of the viscosity of the resin composition. The solid content is measured by the method described in the Examples below.

[0118] The viscosity of the resin composition measured at 25° C. with a Gardner bubble viscometer (hereinafter also referred to as “Gardner viscosity”) is Z or less, preferably W or less, more preferably V or less, and even more preferably T or less. The viscosity of the resin composition measured with a B-type viscometer at 25°C (hereinafter also referred to as "B-type viscosity") is preferably less than 5000 mPa·s, more preferably less than 3000 mPa·s, even more preferably less than 2000 mPa·s, and particularly preferably less than 1000 mPa·s. When the viscosity (B-type viscosity or Gardner viscosity) of the resin composition is equal to or lower than the upper limit, an antifouling agent and the like can be blended or the resin composition can be painted without further adding an organic solvent for dilution, and a coating composition with a low VOC content can be obtained. The resin composition preferably has a viscosity at a solid content of at least 50 mass % that is equal to or lower than the above-mentioned preferred upper limit. The lower limit of the viscosity of the resin composition is not particularly limited. From the viewpoint of preventing paint sagging during application, the Gardner viscosity at 25°C is preferably B or more, and the B-type viscosity at 25°C is preferably 100 mPa s or more. Therefore, the Gardner viscosity of the resin composition at 25°C is preferably equal to or greater than B and equal to or less than Z. The B-type viscosity of the resin composition at 25°C is preferably equal to or greater than 100 mPa·s and less than 5000 mPa·s, more preferably equal to or greater than 100 mPa·s and less than 3000 mPa·s, even more preferably equal to or greater than 100 mPa·s and less than 2000 mPa·s, and particularly preferably equal to or greater than 100 mPa·s and less than 1,000 mPa·s.

[0119] The viscosity of the resin composition can be adjusted by the solid content of the resin composition (content of copolymer (X), copolymer (Y) and other components), weight average molecular weight of copolymer (X) and copolymer (Y), glass transition temperature, presence or absence of crosslinked structure, etc. For example, the lower the solid content, particularly the content of copolymer (X) and copolymer (Y), the lower the viscosity tends to be. Also, the smaller the weight average molecular weight of copolymer (X) and copolymer (Y) or the lower the glass transition temperature, the lower the viscosity tends to be.

[0120] The resin composition can be prepared, for example, by producing the copolymer (X) and the copolymer (Y) as described above, and adding an organic solvent and other components as necessary, and mixing them. When the copolymer (X) and the copolymer (Y) are produced by a solution polymerization method, it is not necessary to add an organic solvent.

[0121] <Action and effect> In the resin composition described above, by making the copolymer (X) and the copolymer (Y) have a specific composition, a coating film exhibiting excellent antifouling effect can be formed. In addition, a coating film having high hardness can be formed. In addition, a resin composition having good storage stability can be obtained without the varnish becoming cloudy during storage.

[0122] The copolymer (X) contains the structural unit (A) and has a structure (I) in which the carboxyl group is protected by a specific group, which makes it hydrolyzable in seawater, etc. The copolymer (Y) has a hydrolyzable group and can be hydrolyzed in seawater or the like. Therefore, the coating film containing the copolymer (X) and the copolymer (Y) exhibits self-polishing properties in seawater or the like.

[0123] That is, copolymer (X) has structure (I), and in this state it does not dissolve in seawater, but when structure (I) is hydrolyzed upon contact with seawater, carboxyl groups and the like are generated and it dissolves in seawater. As a result, the coating surface gradually dissolves in seawater and the surface is renewed (self-polished). The structure (I), triorganosilyloxycarbonyl group, and structure (II) of copolymer (Y) do not dissolve in seawater in this state, but when they come into contact with seawater and undergo hydrolysis, carboxyl groups and other groups are generated, which dissolve in seawater. As a result, the coating surface gradually dissolves in seawater and undergoes surface renewal (self-polishing).

[0124] In addition, the copolymer (X) contains the structural unit (B) and thus has a polysiloxane block. Therefore, a coating film containing the copolymer (X) is less susceptible to adhesion of marine organisms and other fouling, and exhibits excellent antifouling effects even when the coating film does not contain an antifouling agent. When an antifouling agent is contained, the coating film undergoes surface renewal, so that the antifouling agent is always exposed on the coating film surface, and the antifouling effect of the antifouling agent is stably exhibited for a long period of time.

[0125] In addition, the copolymer (X) has a combination of a specific amount of the structural unit (A) containing the hydrophilic structure (I) as a hydrolyzable structure and a specific amount of the structural unit (B) containing a hydrophobic polysiloxane block, which provides a more excellent long-term antifouling effect. This is thought to be because the inclusion of a specific amount of the hydrophilic structure (I) and a specific amount of the hydrophobic polysiloxane block causes the coating film to become a phase-separated film, and repeated hydrolysis of only the coating film surface layer is suppressed to prevent excessive dissolution and swelling of the coating film, resulting in a stable, long-term excellent antifouling effect.

[0126] As described above, when other resins are blended with a resin composition containing a copolymer containing a specific amount of the hydrophilic structure (I) and a specific amount of the hydrophobic polysiloxane block and an organic solvent, the varnish becomes cloudy and has low storage stability. In contrast, by blending copolymer (X) with a copolymer having a hydrolyzable group such as copolymer (Y), the compatibility between the polymers becomes good, and a resin composition having good coating hardness and good storage stability can be obtained without impairing the antifouling property, which is the performance required for an antifouling coating material.

[0127] Because of the above effects, the resin composition is suitable for use as a coating composition, particularly as an antifouling coating composition. The resin composition can be used as a coating composition as is, or mixed with an antifouling agent, etc., as necessary. However, the use of the resin composition is not limited thereto, and it can also be used for purposes other than coating compositions.

[0128] [Paint composition] A coating composition according to one embodiment of the present invention contains the above-mentioned resin composition, and contains copolymer (X), copolymer (Y), and an organic solvent. The copolymer (X), the copolymer (Y) and the organic solvent are the same as those described above. The coating composition may contain one or more types of copolymer (X) and copolymer (Y), as well as the organic solvent. The coating composition may further contain other components in addition to the copolymer (X), the copolymer (Y) and the organic solvent, as necessary. At least a part of the components contained in the coating composition is derived from the resin composition. A part of the components contained in the coating composition may be those not derived from the resin composition (those blended during the production of the coating composition).

[0129] <Other ingredients> The coating composition may further contain silicone oil. When the coating composition contains silicone oil, the coating film formed has better antifouling properties. Examples of silicone oils include straight silicone oils such as dimethyl silicone oil, methylphenyl silicone oil, and methylhydrogen silicone oil, and modified silicone oils. Modified silicone oils are silicone oils in which an organic group other than a methyl group and a phenyl group (hereinafter also referred to as a "modified group") is introduced into a part of the silicon atoms of straight silicone oils. Examples of the modified group include a chlorophenyl group, a methylstyrene group, a long-chain alkyl group (e.g., an alkyl group having 2 to 18 carbon atoms), a polyether group, a carbinol group, an aminoalkyl group, an epoxy group, and a (meth)acryloyl group. Any one of these silicone oils can be used alone, or two or more can be used in combination. Among the above silicone oils, polyether-modified silicone oils having a polyether group as a modified group are preferred from the viewpoint of antifouling properties.

[0130] As the silicone oil, commercially available products can be used. Examples of commercially available silicone oils include "KF-96", "KF-50", "KF-54", "KF-56", and "KF-6016" (all manufactured by Shin-Etsu Chemical Co., Ltd.), "TSF451" (manufactured by Momentive Performance Materials), "Fluid47" (manufactured by Rhoneplan (France)), "SH200", "SH510", "SH550", "SH710", "DC200", "ST-114PA", and "FZ209" (all manufactured by Dow Corning Toray Co., Ltd.).

[0131] The coating composition may further contain an antifouling agent from the viewpoint of the antifouling properties of the coating film. When the coating composition contains an antifouling agent, the antifouling properties of the coating film formed are more excellent. The antifouling agent includes inorganic antifouling agents, organic antifouling agents, etc., and one or more of them can be appropriately selected and used depending on the required performance. Specific examples of the antifouling agent include copper-based antifouling agents such as cuprous oxide, copper thiocyanate, and copper powder, compounds of other metals (lead, zinc, nickel, and the like), amine derivatives such as diphenylamine, nitrile compounds, benzothiazole-based compounds, maleimide-based compounds, pyridine-based compounds, etc. These can be used alone or in combination of two or more.

[0132] More specifically, examples of the antifouling agent include 4-bromo-2-(4-chlorophenyl)-5-(trifluoromethyl)-1H-pyrrole-3-carbonitrile, manganese ethylene bisdithiocarbamate, zinc dimethyl dithiocarbamate, 2-methylthio-4-t-butylamino-6-cyclopropylamino-s-triazine, 2,4,5,6-tetrachloroisophthalonitrile, N,N-dimethyldichlorophenylurea, zinc ethylene bisdithiocarbamate, copper rhodanide, 4,5-dichloro-2-n-octyl-4-isothiazolin-3-one, N-(fluorodichloromethylthio)phthalimide, N,N'-dimethyl-N'-phenyl-(N-fluorodichloromethylthio) Examples of such compounds include sulfamide, 2-pyridinethiol-1-oxide zinc salt (also known as "zinc pyrithione"), tetramethylthiuram disulfide, Cu-10%Ni solid solution alloy, 2,4,6-trichlorophenylmaleimide 2,3,5,6-tetrachloro-4-(methylsulfonyl)pyridine, 3-iodo-2-propynyl butylcarbamate, diiodomethyl paratolyl sulfone, bisdimethyldithiocarbamoylzinc ethylene bisdithiocarbamate, phenyl(bispyridyl)bismuth dichloride, 2-(4-thiazolyl)-benzimidazole, medetomidine, pyridinetriphenylborane, and 4,5-dichloro-2-n-octyl-isothiazolin-3-one.

[0133] Among the above, from the viewpoint of antifouling properties, it is preferable that the antifouling agent contains at least one selected from the group consisting of cuprous oxide, 4-bromo-2-(4-chlorophenyl)-5-(trifluoromethyl)-1H-pyrrole-3-carbonitrile (hereinafter also referred to as "antifouling agent (d1)"), medetomidine, and 4,5-dichloro-2-n-octyl-isothiazolin-3-one. When cuprous oxide and the antifouling agent (d1) are combined, the ratio (mass ratio) thereof, cuprous oxide / antifouling agent (d1), is preferably 80 / 20 to 99 / 1, and more preferably 90 / 10 to 99 / 1. At least one selected from the group consisting of cuprous oxide, the antifouling agent (d1), medetomidine, and 4,5-dichloro-2-n-octyl-isothiazolin-3-one may be combined with other antifouling agents.

[0134] The coating composition may contain a silicon compound such as dimethylpolysiloxane (excluding silicone oil) or a fluorine-containing compound such as a fluorinated hydrocarbon, for the purpose of imparting lubricity to the coating surface and preventing adhesion of organisms.

[0135] The coating composition may contain various pigments, defoamers, leveling agents, pigment dispersants (e.g., anti-settling agents), anti-sagging agents, matting agents, UV absorbers, antioxidants, heat resistance improvers, slip agents, preservatives, plasticizers, viscosity control agents, and the like.

[0136] The crack resistance and peel resistance of the coating film can be improved by adding a plasticizer to the coating composition. Chlorinated paraffin is preferred as the plasticizer because it is effective in improving the crack resistance and peel resistance of the coating film. In that they function as anti-settling agents and anti-dripping agents and provide the effect of improving the storage stability and pigment dispersibility of the coating composition, organic waxes such as semi-synthetic waxes and synthetic waxes are preferred, and polyethylene waxes, oxidized polyethylene waxes, and polyamide waxes are more preferred.

[0137] Examples of pigments include zinc oxide, talc, silica, barium sulfate, potassium feldspar, aluminum hydroxide, magnesium carbonate, mica, carbon black, red oxide, titanium oxide, phthalocyanine blue, kaolin, gypsum, etc. Zinc oxide and talc are particularly preferred. Examples of anti-settling agents and anti-sagging agents other than thermoplastic resins include bentonite-based agents, finely divided silica-based agents, stearates, lecithin salts, and alkylsulfonates.

[0138] The content of copolymer (X) in the coating composition is preferably 10 to 65 mass%, more preferably 15 to 60 mass%, and even more preferably 20 to 55 mass%, based on the total mass of the coating composition. When the content of copolymer (X) is equal to or more than the lower limit, the antifouling property is more excellent. When the content of copolymer (X) is equal to or less than the upper limit, the coating composition has more excellent coatability.

[0139] The content of the organic solvent in the coating composition can be appropriately set according to the viscosity of the coating composition. For example, it is preferably 65% ​​by mass or less, more preferably 60% by mass or less, and even more preferably 55% by mass or less, based on the total mass of the coating composition. If the content of the organic solvent is equal to or less than the upper limit, the VOC content is sufficiently low.

[0140] When the coating composition contains silicone oil, the content of the silicone oil in the coating composition is preferably 0.1 to 40 mass %, more preferably 1 to 20 mass %, based on the total mass of the coating composition. If the content of the silicone oil is equal to or more than the lower limit, the antifouling property is more excellent. If the content of the silicone oil is equal to or less than the upper limit, the dissolution stability of the coating film is more excellent.

[0141] When the coating composition contains an antifouling agent, the content of the antifouling agent in the coating composition is not particularly limited, but is preferably 10 to 200 parts by mass, more preferably 50 to 150 parts by mass, per 100 parts by mass of the total of the copolymer (X) and the copolymer (Y). When the content of the antifouling agent is equal to or more than the lower limit, the antifouling effect of the coating film formed is more excellent. When the content of the antifouling agent is equal to or less than the upper limit, the coating film properties are more excellent.

[0142] The coating composition can be used to form coating films (antifouling coating films) on the surfaces of substrates such as ships, various fishing nets, port facilities, oil fences, bridges, undersea bases and other underwater structures. A coating film using the coating composition can be formed on the surface of a substrate directly or via an undercoating film. The undercoat film can be formed using a wash primer, a primer such as a chlorinated rubber-based or epoxy-based primer, an undercoat paint, or the like. The coating film can be formed by a known method. For example, the coating composition can be applied to the surface of a substrate or an undercoat on the substrate by brush coating, spray coating, roller coating, immersion coating, or other means, and then dried to form a coating film. The amount of coating composition applied can generally be set to an amount that results in a dry coating film having a thickness of 10 to 400 μm. The coating film can usually be dried at room temperature, and may be dried by heating as necessary.

[0143] <Action and effect> The coating composition described above, like the resin composition described above, can form a coating film that exhibits excellent antifouling effect and has high hardness, and also does not become cloudy during storage and has excellent storage stability. EXAMPLES

[0144] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the examples, "parts" refers to "parts by mass". The evaluations in the examples were carried out by the methods shown below.

[0145] (Solid content (heated residue)) 0.50 g of a sample (resin composition or coating composition) was weighed out onto an aluminum dish, 3 mL of toluene was added with a dropper, and the sample was spread evenly over the bottom of the dish, followed by pre-drying. Pre-drying is a process in which the sample is spread over the entire dish to facilitate the evaporation of the solvent during main drying. In pre-drying, the sample and toluene were heated and dissolved in a water bath at 70 to 80°C, and evaporated to dryness. After pre-drying, main drying was performed for 2 hours in a hot air dryer at 105°C. The solid content (heating residue) was calculated from the mass of the sample before pre-drying (mass before drying) and the mass after main drying (mass after drying) using the following formula. Solid content (mass%) = mass after drying (g) / mass before drying (g) × 100

[0146] (Gardner viscosity) A sample was placed in a dry Gardner bubble viscosity tube (hereinafter simply referred to as a "viscosity tube") up to the indicator line and then corked. The viscosity tube containing the sample was immersed vertically in a thermostatic water bath adjusted to a specified temperature (25.0±0.1°C) for at least 2 hours to keep the sample at a constant temperature, and the viscosity tube serving as the reference tube and the viscosity tube containing the sample were simultaneously rotated 180°, and the viscosity (Gardner viscosity) was determined by comparing the bubble rise rate of the sample with that of the reference tube.

[0147] (Acid value of measurement solution) Approximately 4.0 g of the sample (resin composition) was precisely weighed into a beaker (A(g)), and 50 mL of toluene / 95% ethanol solution (50 / 50 ratio) was added. After stirring for 5 minutes in a sealed container, a Hiranuma automatic titrator (AUTO TITRATOR COM-1600) was used to perform potentiometric titration with 0.5 mol / L potassium hydroxide solution (ethanol solution) manufactured by Kishida Chemical Co., Ltd., whose factor (f) at 20°C is 1.003, and the maximum slope of the titration curve was set as the end point (titration amount = B (mL), titer of KOH solution = f). A blank measurement was also performed in the same manner (titration amount = C (mL)), and the calculation was performed according to the following formula. Measured solution acid value (mgKOH / g)={(BC)×0.5×56.11×f} / A /

[0148] (Weight average molecular weight (Mw), number average molecular weight (Mn)) The weight average molecular weight (Mw) and number average molecular weight (Mn) of the polymer were measured using gel permeation chromatography (GPC) (Tosoh Corporation, HLC-8220). The columns used were TSKgel α-M (Tosoh Corporation, 7.8 mm x 30 cm) and TSKguard column α (Tosoh Corporation, 6.0 mm x 4 cm). The calibration curve was prepared using F288 / F1 / F28 / F80 / F40 / F20 / F2 / A1000 (Tosoh Corporation, standard polystyrene) and styrene monomer.

[0149] (Paint film wear test) The resin solution obtained in each example was applied to a rigid polyvinyl chloride plate of 50 mm x 50 mm x 2 mm (thickness) with an applicator so that the dry film thickness was 120 μm, and then dried to form a coating film, thereby obtaining a test plate. This test plate was attached to a rotating drum placed in seawater and rotated at a peripheral speed of 7.7 m / s (15 knots). This state was maintained for three months, and the film thickness (μm) of the coating film three months after installation was measured. From the measured film thickness, the consumed film thickness after three months (120 μm - measured film thickness) was calculated, and this value was taken as the degree of consumption. The degree of consumption is preferably within the range of 5 to 50 μm / M.

[0150] (Anti-stain properties when left standing) The resin solution obtained in each example was applied with a brush to a sandblasted steel plate previously coated with an anti-rust paint so that the dry film thickness was 200 to 300 μm, and then dried to form a coating film to obtain a test plate. After leaving this test plate stationary for 4 months, the ratio of the area where marine organisms were attached to the total area of ​​the coating film (the area where marine organisms were attached) was examined, and the stationary antifouling properties were evaluated according to the following criteria. ◎: The area of ​​the surface area with marine organisms attached is less than 10%. ○: The area of ​​attached marine organisms is more than 10% but less than 20%. △: The area of ​​adhesion of marine organisms is more than 20% but less than 40%. ×: Area of ​​marine organisms attached is more than 40%.

[0151] (Coating film hardness) The resin solution obtained in each example was applied to a glass substrate using a 500 μm applicator so that the dry film thickness was 80 to 150 μm, and then dried at 25° C. for one week to obtain a test plate on which a coating film was formed. The coating film of this test plate was measured for hardness (Martens hardness) at 25° C. using an ultra-microhardness tester (manufactured by Fisher Instruments, product name: HM2000). The measurement conditions were: dQRST(F) / dt = constant, F (test force) = 10 mN / 10 seconds, C (maximum load creep time) = 5 seconds, maximum indentation load = 10 mN, maximum indentation depth = 6 μm. The coating hardness (Martens hardness) was measured at three different points on the coating of the test plate, and the average value was taken as the hardness of the coating.

[0152] (Transparency of resin solution: storage stability) The resin solution obtained in each example was measured out into a glass bottle, and the appearance was visually confirmed at room temperature.

[0153] (Materials used) PGM: propylene glycol methyl ether. Monomer (M1): A metal atom-containing polymerizable monomer mixture synthesized in Production Example M1 described below. Monomer (M2): A metal atom-containing polymerizable monomer mixture synthesized in Production Example M2 described below. FM-0711: Trade name, manufactured by JNC Corporation (a polysiloxane block-containing polymerizable monomer in the above formula (b1), where v=0, R3a to R3f=methyl groups, w=3, and x=10). X-24-8201: Trade name, manufactured by Shin-Etsu Chemical Co., Ltd. (a polysiloxane block-containing polymerizable monomer in the above formula (b1), where v=0, R3a to R3f=methyl groups, w=3, and x=25). MMA: methyl methacrylate. EA: ethyl acrylate. MTA: 2-methoxyethyl acrylate. BA: n-butyl acrylate. AIBN: 2,2'-azobisisobutyronitrile. AMBN: 2,2'-azobis(2-methylbutyronitrile). Nofumer MSD: Product name, manufactured by NOF Corporation, α-methylstyrene dimer.

[0154] [Manufacturing example M1] A reaction vessel equipped with a stirrer, a temperature regulator, and a dropping funnel was charged with 85.4 parts of PGM and 40.7 parts of zinc oxide, and the temperature was raised to 75° C. while stirring. Then, a mixture consisting of 43.1 parts of methacrylic acid, 36.1 parts of acrylic acid, and 5 parts of water was dropped at a constant rate from the dropping funnel over 3 hours. After stirring for another 2 hours, 36 parts of PGM was added to obtain a transparent metal atom-containing polymerizable monomer mixture (monomer (M1)) with a solid content of 44.8% by mass.

[0155] [Manufacturing example M2] A reaction vessel equipped with a stirrer, a temperature regulator, and a dropping funnel was charged with 72.4 parts of PGM and 40.7 parts of zinc oxide, and the temperature was raised to 75° C. while stirring. Then, a mixture consisting of 30.1 parts of methacrylic acid, 25.2 parts of acrylic acid, and 51.6 parts of Versatic acid was added dropwise at a constant rate over 3 hours from the dropping funnel. After stirring for another 2 hours, 11 parts of PGM were added to obtain a transparent metal atom-containing polymerizable monomer mixture (monomer (M2)) with a solid content of 59.6% by mass.

[0156] [Manufacturing example X-1] 30 parts of xylene, 15 parts of n-butanol, and 4 parts of EA were charged into a reaction vessel equipped with a stirrer, a temperature regulator, and a dropping device, and the temperature was raised to 100 ° C. while stirring. Next, a mixture consisting of 26.6 parts of monomer (M1) (12 parts in terms of solid content), 40 parts of FM-0711, 30.3 parts of MMA, 17.9 parts of EA, 1 part of AIBN, 7.5 parts of AMBN, and 1.5 parts of Nofumer MSD was dropped at a constant speed over 6 hours from the dropping funnel. After the dropwise addition was completed, 0.5 parts of tert-butyl peroxy octoate and 4.0 parts of xylene were dropped at a constant speed over 30 minutes. After stirring for another hour, 16.4 parts of xylene were added. This resulted in a resin composition X-1 containing copolymer X. Table 1 shows the evaluation results of the properties of resin composition X-1 (solid content, acid value of the measured solution, Gardner viscosity immediately after production (hereinafter also referred to as "initial viscosity"), weight average molecular weight and number average molecular weight of the copolymer contained therein) (hereinafter the same). In Table 1, the numerical values ​​in the columns for monomer, initiator, and chain transfer agent indicate the amount (parts) charged. For the amounts of monomers (M1) and (M2) charged, the values ​​in parentheses indicate the amount (parts) charged in solid form, and the values ​​above them indicate the total amount (parts) charged, including the organic solvent.

[0157] [Manufacturing examples X-2~X-7, Y-1~Y-3] Resin compositions X-2 to X-7 and Y-1 to Y-3 were produced in the same manner as in Production Example X-1, except that the type and amount of monomer, the type and amount of initiator were as shown in Table 1, and the amount of solvent initially charged in the reaction vessel and the amount of xylene after the completion of dropwise addition were adjusted according to the respective solid contents.

[0158] [Table 1]

[0159] [Examples 1 to 9, Comparative Example 1] Table 2 shows Examples 1 to 9 and Comparative Example 1 in which resin compositions X-1 to X-7 and Y-1 to Y-3 were used. That is, resin compositions X-1 to X-7 and Y-1 to Y-3 were mixed in the proportions (parts) shown in Table 2 to obtain resin solutions containing the resin compositions and an organic solvent. Table 2 shows the content (unit: mass %) of the structural unit (B) relative to the total mass of all structural units of the copolymer (X) and the copolymer (Y). Table 2 shows the content of copolymer (X), the content of copolymer (Y), and the total content of copolymer (X) and copolymer (Y) relative to the total mass of the resin composition (all in units of mass %). The resin solutions obtained in each example were evaluated for transparency and coating performance (wear and tear, static stain resistance, and coating hardness) by the methods described above. The evaluation results are shown in Table 2.

[0160] [Table 2]

[0161] As shown in Table 2, the resin solutions of Examples 1 to 9 were transparent and had good storage stability. The coating films had good static antifouling properties and coating film hardness. In addition, they had an appropriate degree of wear. On the other hand, in Comparative Example 1, the resin solution was cloudy, the storage stability was low, and the coating hardness was also low. [Industrial Applicability]

[0162] According to the present invention, there can be provided a resin composition which exhibits excellent antifouling effect, is capable of forming a coating film having high coating film hardness, does not become cloudy during storage, and has excellent storage stability. A coating film obtained by using the resin composition of the present invention can be suitably used to prevent adhesion of marine organisms.

Claims

1. A resin composition comprising: a copolymer (X) having at least one kind of structure (I) represented by the following formula (1) or the following formula (2) and a polysiloxane group; and a copolymer (Y) different from the copolymer (X), wherein the copolymer (Y) has a hydrolyzable group. -CO-O-M-O-CO-...(1) ----O-M-R 0 ・・・(2) (In the formula, M represents Zn, Cu, Mg, or Ca; R 0 represents a monovalent organic acid residue.)

2. 2. The resin composition according to claim 1, wherein X / Y, which represents a mass ratio of the copolymer (X) to the copolymer (Y), is 95 / 5 to 40 / 60.

3. The resin composition according to claim 1, wherein the hydrolyzable group of the copolymer (Y) is at least one selected from the group consisting of groups represented by the following formulas (1) to (5) and triorganosilyloxycarbonyl groups: -CO-O-M-O-CO-...(1) ----O-M-R 0 ・・・(2) 【Chemistry 1】 (In the formulas (1) and (2), M represents Zn, Cu, Mg, or Ca; R 0 In formulas (3) to (5), X represents -O-, -S-, or -NR 13 - indicates R 13 represents a hydrogen atom or an alkyl group; R 1’ and R 2’ each represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 3’ and R 5’ each represents an alkyl group, a cycloalkyl group, or an aryl group having 1 to 20 carbon atoms; R 4’ and R 6’ Each represents an alkylene group having 1 to 10 carbon atoms.

4. The resin composition according to claim 1, wherein the copolymer (Y) has an acid value of 20 mgKOH / g or more.

5. 2. The resin composition according to claim 1, wherein, of the copolymer (X) and the copolymer (Y), at least the copolymer (X) has a structural unit (B) based on a monomer having a polysiloxane group and an ethylenically unsaturated bond, and the structural unit (B) is 15 mass% or more and 50 mass% or less with respect to the total mass of all structural units of the copolymer (X) and the copolymer (Y).

6. The resin composition according to claim 1, wherein the copolymer (X) has a structural unit (B) based on a monomer having a polysiloxane group and an ethylenically unsaturated bond, and the structural unit (B) accounts for 15 mass% or more of the total mass of all structural units of the copolymer (X).

7. 2. The resin composition according to claim 1, wherein the copolymer (Y) does not have a structural unit (B) based on a monomer having a polysiloxane group and an ethylenically unsaturated bond, or, if the copolymer (Y) has a structural unit (B), the structural unit (B) accounts for 10 mass% or less of the total mass of all structural units of the copolymer (Y).

Citation Information

Patent Citations

  • Resin composition for Anti-fouling coating material, Anti-fouling coating material, and Anti-fouling film

    WO2013183637A1

  • Polymer-containing composition and stainproof coating composition

    WO2018008166A1

Cited By

  • Game machine

    JP2025105646A

  • Game machine

    JP2025108606A